Accepting a crowdsourced delivery - a choice-based conjoint analysis - Bathke, Henrik; Hartmann, Evi (Proceedings of the Hamburg International Conference of Logistics, 2021)
Purpose: The increase in parcel quantities on the last mile requires new and innovative concepts to support sustainability efforts in urban areas. Crowdsourced delivery (CSD) represents a promising concept as it allows private couriers to take over the parcels’ last mile on trips they would have traveled anyway. Whereas first research on the attributes leading to the acceptance of CSD requests via platforms exists, the attributes’ respective importance remains unclear. Methodology: A choice-based conjoint analysis with 193 respondents willing to participate in CSDs was conducted. Attributes’ relative importance and part-worth utilities were calculated using Hierarchical Bayes estimation. Findings: Results show that differences in deviation of the original travel time and remuneration have the greatest impact on couriers’ request selection, while the degree of familiarity with the recipient and parcel weight are less decisive. Additionally, it became apparent that couriers’ sentimental traits of environmental concerns and extraversion affect the choice of a CSD request. Originality: The study contributes to the scarce literature on the promising concept of CSD to reduce logistics-related environmental externalities and strengthens the application of marketing-related methodologies in logistics research. For CSD platform providers, results enable higher competitiveness through a more individualized request for potential couriers.
CRIS-Team Scopus Importer:2024-12-16

Achieving Competitive Advantage from Sustainable Supplier Management - Insights from the Chemical Industry - Reuter, C.; Foerstl, K.; Hartmann, Evi; Blome, Constantin (International Purchasing & Supply Education & Research Association (IPSERA) Conference, 2009)
WiSo-Import:2015-04-17:1289
Keywords: Innovation

An Agency Theory Perspective on the Purchase of Marketing Services - Tate, Wendy L.; Ellram, Lisa M.; Bals, Lydia; Hartmann, Evi; van der Valk, Wendy (Industrial Marketing Management, 2010)
<span style="color: rgb(46, 46, 46); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; word-spacing: -1.24453px;">The purchase of business services has become an important part of organizations' acquisition of external resources, and is therefore receiving growing scholarly attention. The supply management function is increasingly supporting more complex service purchases, including a wide range of marketing services. The trend to involve supply management in the purchase of these complex business services is partially being driven by increasing awareness of the value of applying standard purchasing techniques to the purchase of these non-standard items. The purchase of such services has historically been managed by content experts, with limited involvement of supply management. However, the involvement of supply management in these purchases is driving the content experts to adopt a more facilitating relationship in which both areas interact with the supplier. This research uses Agency Theory as a lens to look at the Agency Triad among supply management, marketing, and suppliers. Elaborating on prior seminal work, the basic tenets of Agency Theory and its assumptions regarding human behavior are combined with the results of a focus group and case studies to develop propositions on the design of contractual arrangements between two Principals (marketing and supply management) and a single Agent who provides marketing services.
Keywords: Marketing services; Supply management; Service purchasing; Agency Theory

An Empirical Study on Sourcing in Emerging Countries from the Resource-based View - Hartmann, Evi; Bals, Lydia; Kaiser, Gernot (2008 Academy of Management Annual Meeting, 2008)
WiSo-Import:2015-04-17:1298
Keywords: Innovation

An Integrated Framework for Supply Performance Measurement - Hartmann, Evi; Entchelmeier, Aiko; Henke, Michael (Performance excellence - Zeitschrift für Controlling und Innovationsmanagement, 2007)
WiSo-Import:2015-03-26:1237
Keywords: Innovation

Assessment sharing intra-industry strategic alliances: Effects on sustainable supplier management within multi-tier supply chains - Lechler, Sabrina; Canzaniello, Angelo; Hartmann, Evi (International Journal of Production Economics, 2019)
Focal companies have to manage both first-tier suppliers and lower-tier suppliers in order to prevent reputational damage due to sustainability violations in their supply chains. However, the involvement of sub-suppliers in supplier management practices creates new challenges, which can be managed more effectively in collaboration with other firms. Therefore, the purpose of this study is to explore from an extended agency theory perspective how companies collaborate within assessment sharing strategic alliances (ASSAs) to manage suppliers with respect to sustainability and to reveal the resultant effects on the management of suppliers within multi-tier supply chains. Therefore, an embedded multiple case study with multiple units of analysis was conducted. Results show that, dependent on the experience in ASSAs, supplier assessment and optionally supplier collaboration practices are executed collaboratively among the members of those strategic alliances to improve suppliers' compliance with the focal company's corporate sustainability standards. However, the configuration of jointly executed activities as well as membership conditions vary between strategic alliances and consequently influence the effects on supplier management. Nevertheless, the observations revealed that the causes for agency risk, namely information asymmetry and goal conflicts, can be mitigated through collaboration within ASSAs and thus multi-tier suppliers' compliance with corporate sustainability standards is fostered.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Agency theory; Lower-tier supplier; Multi-tier supply chain management; Multiple case study design; Strategic alliance; Sub-supplier

Asset Management in Chemicals and Pharmaceuticals: The Value of Building Efficient Production Networks - Hartmann, Evi; Naujok, N.; Bäumler, M; Neff, P.; Vallerien, S. (Chemical Market Reporter, 2001)
WiSo-Import:2015-03-26:1248
Keywords: Innovation

A systematic assessment of supplier selection literature–State-of-the-art and future scope - Wetzstein, Anton; Hartmann, Evi; Benton jr., W.C.; Hohenstein, Nils Ole (International Journal of Production Economics, 2016)
With the growth in outsourcing in various sectors, the selection of the right suppliers is increasingly critical to a firm's business success. However, a thorough analysis of the extensive spectrum of supplier selection literature has not yet been performed. To address this gap, we conduct a comprehensive and systematic literature review. The purpose is to examine in detail the evolution of the extensive body of research, its research streams and areas for further research. We developed a classification framework that contains six streams of research derived from the extensive literature comprising both a quantitative and qualitative content analysis. To this end, this paper contributes a structured, large-scale and longitudinal review of 221 papers published in leading journals from 1990 to 2015 and carefully elaborated research recommendations to further advance supplier selection. Results reveal tremendous scientific progress in the last two decades, a trend predicted to continue. Moreover, the findings show that particular streams have been strongly accentuated whereas other important aspects lack examination. Research on mathematical approaches clearly dominates the body of supplier selection. Green and sustainable as well as strategy oriented supplier selection are at an early stage of the research cycle and represent upcoming streams. Contextual perspectives, such as behavioral aspects, theoretical foundation, or multi-period/ longitudinal settings also require further attentio
Keywords: Vendor selection; Framework; Methods; Strategic Supplier Selection; Supply management; Systematic literature review

A Theory-Based Framework for Integrated Supply Performance Measurement - Hartmann, Evi; Entchelmeier, Aiko; Henke, Michael; Jahns, Christopher (Strategische Bedeutung der Produktion, 2007)
WiSo-Import:2015-04-20:1255
Keywords: Innovation

Barriers of purchasing departments' involvement in marketing service procurement - Bals, Lydia; Hartmann, Evi; Ritter, Thomas (Industrial Marketing Management, 2009)
A considerable part of firms' marketing services are supplied by external providers, e.g. advertisement agencies, printing houses, trade fair exhibition builders. Although a large spend category, low involvement of purchasing departments prevails during the procurement decision process. This paper develops a conceptual model of purchasing departments' involvement in marketing service procurement along the dimensions “breadth along process” and “depth of integration”, thus contributing to the measurement of purchasing departments' involvement. Drawing on the findings of a case study, we further propose that the impact of purchasing departments' involvement on procurement success is moderated by procurement complexity, and the duration of the relationship between the purchasing and marketing employees. In addition, barriers to purchasing departments' involvement are conceptualized as lack of skills, lack of motivation, and lack of opportunity.
WiSo-Import:2015-03-26:1015
Keywords: Service; Purchasing; Procurement; Marketing; Involvement; Integration

Barriers to interaction and collaboration of marketing and purchasing functions - Bals, Lydia; Hartmann, Evi; Ritter, Thomas (IPSERA German Node Conference, 2007)
WiSo-Import:2015-04-17:1304
Keywords: Innovation

Being a female leader in modern logistics: A qualitative research on female empowerment in the logistics industry - Küffner, Christoph; Bathke, Henrik; Hartmann, Evi (31. IPSERA Konferenz, 2022)

Benchmarking Ground Handling Services at European Hub Airports - Schmidberger, S.; Bals, Lydia; Hartmann, Evi; Jahns, Christopher (International Purchasing & Supply Education & Research Association (IPSERA) Conference, 2009)
WiSo-Import:2015-04-17:1290
Keywords: Innovation

Benchmarking of Ground Handling Services at Major Airports - Hartmann, Evi; Schmidberger, S.; Gaida, B. (German Aviation Research Society (GARS), 2005)
WiSo-Import:2015-04-17:1334
Keywords: Innovation

Beschaffung im Handel - Eine Unternehmensfunktion im Wandel - Jahns, Christopher; Hartmann, Evi; Entchelmeier, Aiko (Jahrbuch Handelsforschung, 2007)
WiSo-Import:2015-04-20:1260
Keywords: Innovation

Big data in supply chain management: A Delphi-based analysis - Roßmann, Bernhard; Canzaniello, Angelo; von der Gracht, Heiko; Hartmann, Evi (Annual International Purchasing & Supply Education & Research Association (IPSERA) Conference, 2017)

Blockchain technology enabling the Physical Internet: A synergetic application framework - Meyer, Tobias; Kuhn, Marlene; Hartmann, Evi (Computers & Industrial Engineering, 2019)

Blockchain Technology in Logistics and Supply Chain Management - A Bibliometric Literature Review from 2016 to January 2020 - Müßigmann, Benjamin; Von Der Gracht, Heiko; Hartmann, Evi (IEEE Transactions on Engineering Management, 2020)
As part of business and management studies, research works addressed blockchain technology (BCT) in logistics and supply chain management (LSCM) first in 2016. Increasing levels of interest from researchers and practitioners alike have led to an increasing number of studies from both ends; however, a thorough bibliometric- and cocitation network analysis of BCT in LSCM research has not been carried out so far. To address this gap and to build a basis for future research endeavors, this article provides a bibliometric analysis on BCT, comprising data from 613 articles from academic supply chain research. It is therefore an easy-to-access entry point for academics and practitioners into the topic of BCT in LSCM. This study aims to understand the status of research of BCT in LSCM. To present the results, this article employs a bibliometric analysis methodology. It adopts a citation network analysis and a cocitation analysis. Based on a cocitation analysis, this article classifies the existing literature into five different research clusters, including theoretical sensemaking, conceptualizing and testing blockchain applications, framing BCT into supply chains, the technical design of BCT applications for real-world LSCM applications, and the role of BCT within digital supply chains.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Bibliometrics; blockchain; citation network analysis; cocitation network analysis; logistics; supply chain management

Building Resilience Through Foresight: The Case of Maritime Container Shipping Firms - Bathke, Henrik; Münch, Christopher; von der Gracht, Heiko A.; Hartmann, Evi (IEEE Transactions on Engineering Management, 2022)
Maritime container shipping (MCS) firms represent the backbone of worldwide supply chains. Due to the emergence of global trends and disruptions, MCS firms increasingly face an uncertain environment. Consequently, MCS firms must develop dynamic capabilities to enable the reconfiguration of organizational resources for building resilience in a constantly changing business ecosystem. To create adequate dynamic capabilities, MCS firms need to anticipate the future of their macro environment through advanced foresight techniques. Using a Delphi-based scenario analysis, this study systematically examines scenarios for MCS firms’ macro environment. Twelve projections for the MCS industry were systematically created and were then assessed by 51 maritime experts. The resulting three distinct scenarios deliver valuable insights for MCS firms’ executives, whereas the blockchains and drones technology will have already increased efficiency in the short-term scenario “picking the low-hanging fruit,” other technological disruptions will only affect the industry in the medium-term scenario “experiencing an era of dichotomy.” In the long-term scenario “overcoming the obstacles of the generational shift,” MCS firms will experience a transfer toward alternative fuel powered and autonomously driven vessels. Offering detailed scenarios for the future MCS macro environment, this study represents a guide for decision-makers on how to create dynamic capabilities in MCS firms to build resilience. Moreover, the results revealed differences in the experts’ assessments due to their characteristics. Therefore, the study contributes to the academic focus on in-depth diversity analysis in the Delphi methodology and emphasizes the relevance of incorporating multiple stakeholders and panelists in future plannin
Keywords: COVID-19; Delphi; freight transportation; judgmental forecasting; maritime; scenarios; technology foresight

Capabilities of digital servitization: Evidence from the socio-technical systems theory - Münch, Christopher; Marx, Emanuel; Benz, Lukas; Hartmann, Evi; Matzner, Martin (Technological Forecasting and Social Change, 2022)
Driven by pressures for sustainable development and disruptions such as the COVID-19 pandemic, manufacturing companies in the 21st century are affected by two intertwined trends: Industry 4.0 and servitization. Digital servitization, which represents the transition from providing products to offering smart product-service systems, is currently seen as a black box by companies confronting them with major challenges. Current literature has not yet investigated which capabilities are required for the development and provision of smart PSSs. To address this gap, an exploratory multiple case study was performed using semi-structured interviews with 18 representatives of four manufacturing companies and six representatives of companies in a supporting role. A socio-technical systems perspective was adopted to cover the interconnectedness and complementarity of internal and external elements relevant for providing a smart PSS. The study identified 46 capabilities of digital servitization to offer and perform smart PSSs and systemically classified these within the dimensions of the socio-technical systems theory, thus providing companies with numerous insights into successful digital servitization. The results contribute to the practical and academic understanding of digital servitization by outlining capabilities to offer and perform smart PSSs and providing support for the use of socio-technical systems theory to frame these capabilities systematically.
Keywords: Digital servitization; Industry 4.0; Smart product-service system; Smart PSS; Manufacturing

Characterizing and measuring performance in purchasing marketing services - Bals, Lydia; Hartmann, Evi (16th International Purchasing & Supply Education & Research Association (IPSERA), 2007)
WiSo-Import:2015-04-17:1302
Keywords: Innovation

Co-creating value in the automotive supply chain: an RFID application for processing finished vehicles - Herrmann, Stefanie; Rogers, Helen; Gebhard, Marina; Hartmann, Evi (Production Planning & Control, 2015)
The aim of this study was to investigate the capability of a radio-frequency-identification (RFID)-based information system in the international distribution process of a car manufacturer. This innovative cross-company RFID application has been developed, implemented and evaluated in practice and reported here in the form of a case study. The results show that RFID applied to this application is mature enough for use in a manufacturing industry setting and furthermore that it generates significant benefits for the entire distribution supply chain. This research provides practitioners with insights into a successful RFID application by presenting criteria for hardware selection and the design of the system and testing phase. It also highlights the shared benefits available to supply chain partners. Further research is needed to develop greater standardisation for a network-wide data exchange and to develop cost-benefit sharing concept
Keywords: RFID; cross-company; application; automotive; industry; co-creation; supply; chain

Constituting dimensions of early internationalizing firms: Towards a common framework - Bals, Lydia; Berry, Heather; Hartmann, Evi; Rättich, Gordian (2010)
From both an entrepreneurial and international business vantage point, quick and early internationalization of firm value chain activities can allow firms to be as efficient, effective and competitive as possible right from the start. Nevertheless, the terms used to describe early internationalizing firms, as for example "born globals" or "international new ventures", currently have a multitude of interpretations and operationalizations. Based on a systematic literature review, we propose four criteria to distinguish these firms, including timing of foreign entry, business functions, ownership, and extent of multinationality. Thus, we seek to extend the current discussion and research efforts and embrace a broader perspective based on extant literature on early internationalizing firms.
WiSo-Import:2015-04-17:1274
Keywords: Innovation

Context-dependency of Purchasing and Supply Management: An empirical Institutional Theory Approach - Kerkfeld, Dieter; Hartmann, Evi (70th Annual Meeting of the Academy of Management - Dare to Care: Passion and Compassion in Management Practice and Research, AOM 2010, 2010)
Within the operations management literature a strong body of knowledge exists about the contribution of purchasing and supply management (PSM) to performance but little attention has been given to the potential influence of contextual factors on purchasing maturity and its relationship on performance. This study is rooted in institutional theory to formulate a number of propositions about contextual factors. First, we develop and empirically test a structural equation modeling (SEM) model of the influence of purchasing maturity to both operational performances and to business profitability. Purchasing maturity comprises four strategic PSM practices, supplier management, performance management, talent management, and cross-functional integration. The operational performances measure PSM's contribution to cost reductions, quality improvements, and innovation. Second, we analyze the influence of three contextual factors industry sector, degree of centralization, and reporting level of the chief purchasing officer (CPO) on the implemented level of purchasing maturity and its relationship on performance. This study combines multiple data sources, from telephone interviews, questionnaires, and objective financial data collected from a global, cross-industry sample of 306 major companies. Our results confirm that a sophisticated purchasing maturity has a positive impact on operational performance as well as an indirect positive effect on business profitability. Furthermore, the results indicate that both the implementation of purchasing maturity and its relationship on performance are to some degree context-dependent. This study provides CPOs with insights on how to improve and audit PSM's contribution towards performance, which is increasingly important during the current economic crisis.
WiSo-Import:2015-04-17:1276
Keywords: Innovation

Corporate Social Responsibility in Buyer-Supplier Relationships: Is it Beneficial for Top-Tier Suppliers to Market their Capability to Ensure a Responsible Supply Chain? - Leppelt, Thomas; Foerstl, K.; Hartmann, Evi (Business Research, 2013)
WiSo-Import:2015-03-26:4750

Cross-Functional Integration and Functional Coordination in Purchasing and Supply Management: Antecedents and Effects on Purchasing and Firm Performance - Foerstl, K.; Hartmann, Evi; Wynstra, F.; Moser, Roger (International Journal of Operations & Production Management, 2013)
Purpose: The purpose of this paper is to develop a set of nine hypotheses linking four purchasing and supply management (PSM) practices directly to purchasing performance and indirectly to financial performance. Design/methodology/approach: The authors collected data in a global cross-industry survey of 148 companies, combining primary interview and survey data with secondary data on firm performance, in order to minimize the impact of common method variance. Findings: Support was found for eight of the nine hypotheses. In particular, a positive impact was found of cross-functional integration and functional coordination on purchasing performance, and of purchasing performance on firm performance. Both talent management and performance management have a positive impact on cross-functional integration and functional coordination. Talent management also has a direct impact on purchasing performance, in contrast to performance management. Originality/value: The association of enhanced PSM maturity levels with financial performance metrics collected from secondary data sources provides robust empirical support for the stated but to this point largely untested positive impact of PSMmaturity on the firm's competitive position. © Emerald Group Publishing Limited.
WiSo-Import:2015-03-26:4549
Keywords: Cross-functional integration; Financial performance; Functional coordination; Path analysis; Purchasing; Purchasing and supply management; Supply chain management

Cross-Functional Integration and Functional Coordination in Purchasing and Supply Management - Foerstl, K.; Hartmann, Evi; Wynstra, F. (Academy of Management Annual Meeting, 2009)
WiSo-Import:2015-04-17:1285
Keywords: Innovation

Defusing the Supply Chain: How the Application of IoT Changes SCRM - Birkel, Hendrik; Hartmann, Evi (Academy of Management Proceedings, 2019)

Der Beitrag des Einkaufs zum Unternehmenserfolg wird unterschätzt - Hartmann, Evi (Einkauf & Supply Management. Highlights and Hot Spots, 2006)
WiSo-Import:2015-04-20:1263
Keywords: Innovation

Der Einkauf von Dienstleistungen im Visier der Kosten-Marshalls - Jahns, Christopher; Hartmann, Evi (Beschaffung aktuell, 2007)
Unter den Dauerrivalitäten im Business zeichnen sich insbesondere die Nickeligkeiten zwischen Marketing und Einkauf durch ihren legendären Unterhaltungswert aus. „Die haben doch noch nie aufs Geld geschaut“, lautet der Standardvorwurf vom Einkauf Richtung Marketing, während sich Marketing revanchiert mit: „Die machen uns die ganze Kreativität kaputt mit ihrer Kostenschinderei!“ Sind Marketing und Einkauf natürliche Feinde? Natürlich nicht.
WiSo-Import:2015-03-26:1239
Keywords: Innovation

Der Mega-Hub - Hartmann, Evi (Logistics und Supply Chain Management - Highlights und Hot Spots, 2006)
WiSo-Import:2015-04-20:1262
Keywords: Innovation

Designing comprehensive purchasing training – A conceptual framework - Feisel, Edda; Hartmann, Evi; Schober, Holger; Giunipero, Larry (24th Industrial Marketing and Purchasing (IMP) conference, 2008)
WiSo-Import:2015-04-17:1295
Keywords: Innovation

Determining the Purchase Situation: A Comprehensive View on Customer Behaviour - Hartmann, Evi; Ritter, Thomas; Gemünden, Hans Georg (Journal of Consumer Behaviour, 2004)
Customer behaviour has moved to the agenda of suppliers' senior management reflecting an increasing strategic attention to benefits that can be gained from management of and cooperation with customers. However, these benefits can only be achieved if the seller's suggested interaction mode matches the purchasing situation of the customer because different approaches are suitable for different purchase situations, i.e. for the specific circumstances the buying firm is in. In this paper, different classification models of purchase situations are analysed in order to identifying the underlying dimensions. Based on a literature review, the authors group the indicators in four dimensions. Then by combining these dimensions an overall integrated classification model is developed.
WiSo-Import:2015-03-26:1230
Keywords: Innovation

Determining the Purchase Situation: Cornerstone of Supplier Relationship Management - Hartmann, Evi; Ritter, Thomas; Gemünden, Hans Georg (17th Industrial Marketing and Purchasing (IMP) conference, 2001)
WiSo-Import:2015-04-17:1343
Keywords: Innovation

Development of a performance measurement system for the benchmarking of ground handling services at European hub airports - Jahns, Christopher; Hartmann, Evi; Schmidberger, S. (12th International Symposium on Logistics (ISL), 2007)
WiSo-Import:2015-04-17:1314
Keywords: Innovation

Development of a Risk Framework for Industry 4.0 in the Context of Sustainability for Established Manufacturers - Birkel, Hendrik; Veile, Johannes; Müller, Julian; Hartmann, Evi; Voigt, Kai-Ingo (Sustainability, 2019)
The concept of “Industry 4.0” is expected to bring a multitude of benefits for industrial value creation. However, the associated risks hamper its implementation and lack a comprehensive overview. In response, the paper proposes a framework of risks in the context of Industry 4.0 that is related to the Triple Bottom Line of sustainability. The framework is developed from a literature review, as well as from 14 in-depth expert interviews. With respect to economic risks, the risks that are associated with high or false investments are outlined, as well as the threatened business models and increased competition from new market entrants. From an ecological perspective, the increased waste and energy consumption, as well as possible ecological risks related to the concept “lot size one”, are described. From a social perspective, the job losses, risks associated with organizational transformation, and employee requalification, as well as internal resistance, are among the aspects that are considered. Additionally, risks can be associated with technical risks, e.g., technical integration, information technology (IT)-related risks such as data security, and legal and political risks, such as for instance unsolved legal clarity in terms of data possession. Conclusively, the paper discusses the framework with the extant literature, proposes managerial and theoretical implications, and suggests avenues for future research.<br

Development of a search and rescue framework for maritime freight shipping in the Arctic - Benz, Lukas; Münch, Christopher; Hartmann, Evi (Transportation Research Part A-Policy and Practice, 2021)
In recent years, Arctic routes have been receiving increasing attention, as they offer a solution to capacity bottlenecks on the most frequented routes, such as the Suez Canal, Strait of Malacca, and Panama Canal. Due to climate change and melting polar ice, Arctic routes, especially the Northern Sea Route/Northeast Passage and Northwest Passage, are becoming increasingly competitive. The consequence of this development is an increase in maritime traffic in Arctic waters. Due to the harsh environment, maritime activities in the Arctic are associated with numerous risks, as reflected in the 512 incidents in the last decade. Therefore, sufficient search and rescue capabilities are necessary to ensure safety. Thus far, various studies have focused on different components of search and rescue, such as port infrastructure, icebreaker capabilities, and navigation. However, there is no study offering a framework for the required further development of search and rescue capabilities. Therefore, in this paper, a search and rescue framework is proposed. The development of the framework is based on a literature review of dimensions of search and rescue in the Arctic. Semi-structured interviews with 24 experts regarding the identified dimensions were conducted. The results of the qualitative content analysis show a total of 23 top-codes and 50 subcodes, which are presented and discussed. The discussion leads to the presentation of the search and rescue framework, including the dimensions port infrastructure, search and rescue equipment, communication technology, navigation technology, standards and agreements, and cooperation and the respective top-codes. Finally, limitations are addressed, and starting points for further research are proposed.<br
Keywords: Arctic shipping; Northern Sea Route; Northwest Passage; Freight shipping; Search and rescue

Die Reserven liegen in der Produktion - Hartmann, Evi; Bäumler, M; Vallerien, S. (Chemie-Produktion, 2002)
WiSo-Import:2015-03-26:1247
Keywords: Innovation

Digital ecosystems and their impact on organizations—A dynamic capabilities approach - Volz, Felix; Münch, Christopher; Küffner, Christoph; Hartmann, Evi (International Journal of Management Reviews, 2025)

Digitalization and its Impact on the Future Role of SCM Executives in Talent Management - An International Cross-Industry Delphi Study - Wehrle, Manuel; Lechler, Sabrina; Von Der Gracht, Heiko A.; Hartmann, Evi (Journal of Business Logistics, 2020)
In the field of supply chain management (SCM), attracting and developing appropriate talent is critical for achieving most SCM goals, as extensive skills are necessary to do the job properly. In order to ensure that future-proof talent can continue to emerge in this discipline, the role of SCM executives is extremely important. Although many studies have been conducted in the field of talent management (TM), the future role of SCM executives has been mostly neglected in research. The present empirical study addresses this gap, taking into consideration the fourth industrial revolution, as innovation in technology continues to drive significant changes in the SCM field. Aiming to investigate the extent to which increasing digitalization is influencing the future role of SCM executives, a Delphi study with 103 experts from industry, academics, and politics/associations was carried out. In order to identify meaningful topic clusters from the data, fuzzy c-means clustering was used. From an actor-network theory perspective, our results show that in some areas of TM, digitalization is leading to a strong fusion of SCM executives and digital technologies, as well as to a clear division of roles, in which either SCM leaders or technology will dominate in the future.
CRIS-Team WoS Importer:2021-01-29

Drivers of supplier sustainability: Moving beyond compliance to commitment - Foerstl, K.; Azadegan, A.; Leppelt, Thomas; Hartmann, Evi (Journal of Supply Chain Management, 2015)

Early Internationalizing Firms: A Revised Framework - Bals, Lydia; Berry, Heather; Hartmann, Evi; Rättich, Gordian (2010)
WiSo-Import:2015-04-17:1275
Keywords: Forschungsbericht 2010; Innovation

Einkauf und Supply Management. Highlights and Hot Spots - Jahns, Christopher; Darkow, Inga-Lena; Hartmann, Evi; Schober, Holger; Walter, S. (Wissenschaft & Praxis, 2006)
WiSo-Import:2015-04-13:1266
Keywords: Innovation

Einkauf von Marketingdienstleistungen: Entwicklung eines integrierten Ansatzes zum Management von Effizienz und Effektivität im Marketing Spend Management - Hartmann, Evi (VHB - WK Produktionswirtschaft Nachwuchstagung, 2006)
WiSo-Import:2015-04-17:1320
Keywords: Innovation

Einkauf von Marketingdienstleistungen: Focus Study Report - Hartmann, Evi; Bals, Lydia (Wissenschaft & Praxis; Smg Publishing, 2007)
Der Einkauf von Dienstleistungen ist weiterhin ein Bereich, in dem viele Unternehmen großes Verbesserungspotential sehen. Unter den Dienstleistungen, die sogenannte "nicht-traditionelle" Kategorien darstellen, steht dabei der Bereich der Marketingdienstleistungen auf einem der vordersten Plätze. In 2006 wurde durch die SMI Focus Group Workshop mit Unternehmensvertretter aus unterschiedlichen Branchen durchgeführt. Der Focus Study Report " Einkauf von Marketingdienstleistungen" führt duch die verschiedenen Aspekte, die dabei diskuiert und erörtert wurden. Fokussiert werden vier wessentliche Schritte der Optimierung von Marketingausgaben aus der Einkaufssicht - der Klärung von Grundlagen , der Identifikation und Analyse von Potenzialen, der Erarbeitung von Lösungskonzepten und der Klärung der Implementierungsvorgehens. Wesentliche Punkte und Ergebnisse zu den verschiedenen Schritten werden im Focus Study Reportpräsentiert.
WiSo-Import:2015-04-13:1254
Keywords: Innovation

Electronic B2B Marketplaces – Impact on B2B Transactions and Relationships? - Oppel, Kerstin; Hartmann, Evi; Lingenfelder, Michael; Gemünden, Hans Georg (17th Industrial Marketing and Purchasing (IMP) conference, 2001)
WiSo-Import:2015-04-17:1344
Keywords: Innovation

Empirical research on the relationships between demand- and supply-side risk management practices and their impact on business performance - Sturm, Sebastian; Hohenstein, Nils-Ole; Birkel, Hendrik; Kaiser, Gernot; Hartmann, Evi (Supply Chain Management-An International Journal, 2021)
Purpose This paper integrates research on demand- and supply-side risk management practices to better explain how to achieve competitive advantage in dynamic business conditions. The purpose of this study is to develop a model linking supply chain flexibility, agility, robustness and resilience and to investigate its relationships and impact on business performance. Design/methodology/approach The authors conduct a review of existing literature to derive their hypotheses and operationalize the respective constructs. The formulated research model is then validated applying partial least squares structural equation modeling on survey data from 89 multi-national companies based in Europe. Findings The authors find a significant positive relationship between supply chain flexibility and supply chain agility as well as supply chain robustness and supply chain resilience, respectively. Additionally, it is argued that supply chain flexibility, agility and resilience have significant positive impact on individual dimensions of business performance. Originality/value The relationships between supply chain flexibility, agility, robustness, resilience and business performance are investigated and empirically validated altogether in a single model for the first time, providing a clear separation of these terms and shedding further light on the management of supply chain risks.
Keywords: supply chain disruption; supply chain flexibility; supply chain agility; supply chain robustness; supply chain resilience; supply chain risk management; demand-side risk management; supply-side risk management; survey data; structural equation modeling; partial least squares

Enabling integrated business planning through big data analytics: a case study on sales and operations planning - Schlegel, Alexander; Birkel, Hendrik; Hartmann, Evi (International Journal of Physical Distribution & Logistics Management, 2020)
Purpose The purpose of this study is to investigate how big data analytics capabilities (BDAC) enable the implementation of integrated business planning (IBP) – the advanced form of sales and operations planning (S&OP) – by counteracting the increasing information processing requirements. Design/methodology/approach The research model is grounded in the organizational information processing theory (OIPT). An embedded single case study on a multinational agrochemical company with multiple geographically distinguished sub-units of analysis was conducted. Data were collected in workshops, semistructured interviews as well as direct observations and enriched by secondary data from internal company sources as well as publicly available sources. Findings The results show the relevancy of establishing BDAC within an organization to apply IBP by providing empirical evidence of BDA solutions in S&OP. The study highlights how BDAC increase an organization's information processing capacity and consequently enable efficient and effective S&OP. Practical guidance toward the development of tangible, human and intangible BDAC in a particular sequence is given. Originality/value This study is the first theoretically grounded, empirical investigation of S&OP implementation journeys under consideration of the impact of BDAC.

Excellence in Purchasing & Supply Management: An empirical study on the impact of purchasing & supply management (PSM) practices on PSM and company performance - Jahns, Christopher; Hartmann, Evi; Widiarta, H.; Moser, Roger; Stolle, M.; Reinecke, N. (15th International Purchasing & Supply Education & Research Association (IPSERA)/17th North American Research/Teaching Symposium (NARS), 2006)
WiSo-Import:2015-04-17:1330
Keywords: Innovation

Exploring barriers towards modular construction – A developer perspective using fuzzy DEMATEL - Feldmann, Finn; Birkel, Hendrik; Hartmann, Evi (Journal of Cleaner Production, 2022)
Modular construction (MC) has been regarded as a feasible solution to significantly improve productivity, shorten building times, and reduce the enormous environmental burden the construction industry has to shoulder. Although there has been considerable uptake of this construction method in several countries worldwide, widespread adoption is still held back by various interlinked barriers. In Germany – one example of a well-established off-site construction (OSC) market – the adoption of MC by housing corporations is still relatively low. This is surprising when considering their key role in quickly creating living spaces in areas with increasing housing shortages. Therefore, this study explores the interconnectedness of MC barriers from a developer's perspective. Based on a literature review, critical barriers (B1–B8) were identified; these barriers were evaluated by industry experts regarding their influence on each other by applying the fuzzy decision-making trial and evaluation laboratory (DEMATEL) approach. The results provide in-depth insights into the relationships of barriers that impede further uptake of MC and highlight the factors that should be given the most attention by practitioners and researchers to promote this cleaner production method. Based on these analyses, the barriers supply (B4), demand (B5), and process (B8) can be regarded as strongly interconnected and highly relevant, while the industry's attitude (B7) is the most critical barrier. In contrast, regulatory (B1) and knowledge (B6) factors are fundamental prerequisites but are largely detached from the network of barriers; therefore, they do not constitute crucial barriers in the context of this study. The technical barrier (B2) has neither strong interconnections in the network nor strong influences on other factors. The financial hurdle (B3) was found to be highly relevant for promoting MC while also being highly influenceable, indicating that there are several possible ways to raise the economic attractiveness of this construction method.<br

Exploring the circular economy paradigm: A natural resource-based view on supplier selection criteria - Münch, Christopher; Benz, Lukas; Hartmann, Evi (Journal of Purchasing and Supply Management, 2022)
The paradigm of circular economy and the transfer of its principles to supply chain management has recently received much attention from researchers and practitioners. Limited natural resources, governmental legislation, and social responsibility for environmental preservation are the main factors for the development of circular supply chains. Especially in the automotive industry, critical materials are used to produce electric vehicles, reinforcing the importance of circularity for the industry. As the first stage of the supply chain, suppliers have a considerable influence on creating self-sufficient production systems, and in the automotive sector, a low level of vertical integration is important. Therefore, selecting suppliers is an enabler for circular supply chains, but this decision is a complex process due to multiple, partly conflicting criteria. To contribute to the knowledge in this research area, this study applies a fuzzy decision-making trial and evaluation laboratory approach for supplier selection in a circular supply chain in a case study of electric vehicles. First, a set of criteria for supplier selection in circular supply chains was identified based on a literature review and was systematically categorized based on the natural resource-based view. Afterward, the criteria were assessed and refined by experts with a strong procurement background in the automotive industry. Second, the experts were interviewed for value collection, and finally, the mutual influence of the criteria was determined. The results show that the most important criteria for circular supplier selection in electric vehicle supply chains are environmental standards, environmental-related certifications, resource consumption, and waste generation. Regarding the natural resource-based view, short-term focused criteria addressing the capability of pollution prevention have a higher importance compared to long-term criteria that drive sustainable development. In addition, this study classifies the criteria into the categories of causes and effects, discusses the prominence of the criteria, and presents a strategic map showing the mutual influences of the criteria. The results contribute to the theoretical and practical discussion on circular supply chains by identifying the key criteria for circular supplier selection and providing decision-making support for procurement managers.
Keywords: Automotive industry; Circular supply chain; Fuzzy DEMATEL; Multi-criteria decision-making (MCDM); Natural resource-based view; Supplier selection

Frühwarnsysteme im Supply Management: Notwendigkeit, Konzepte und praktische Umsetzung - Jahns, Christopher; Hartmann, Evi; Moder, Marco (12. Magdeburger Logistiktagung, 2006)
WiSo-Import:2015-04-17:1327
Keywords: Innovation

Fuzzy-based decision analysis on Arctic transportation: A guidance for freight shipping companies - Benz, Lukas; Münch, Christopher; Hartmann, Evi (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability, 2021)
Purpose: Due to climate change the Arctic ice is melting, opening new possibilities for the economical use of the Arctic Ocean. However, the decision for shipping companies to transport freight through Arctic waters is based on many factors. The aim of the research is to develop a decision-supporting guidance for shipping companies. Methodology: Based on a literature review and subsequent validation through expert interviews, influencing factors are identified and classified using a framework covering Benefits, Opportunities, Costs, and Risks. A fuzzy set theory to structure multi-criteria decision problems is applied afterward. Findings: The results show that equipment, insurance, and inadequate port infrastructure are the factors with the highest influence in the Costs category and are the most influential factors overall. Security and market potential, the factors with the greatest impact on the Opportunities category, also rank highly as influential overall factors. The strongest Risk factors are weather conditions, delay, and collisions/accidents. The highest influence in the Benefits category are reduced costs. Originality: The influencing factors for Arctic freight shipping have so far only been considered in part with risks focus or other specific aspects, but not in the overall context. To consider multiple perspectives, 24 experts from different domains were involved.
CRIS-Team Scopus Importer:2024-12-16

Fuzzy-based decision analysis on Arctic transportation: A guidance for freight shipping companies - Benz, Lukas; Münch, Christopher; Hartmann, Evi (Proceedings of the Hamburg International Conference of Logistics, 2021)
Purpose: Due to climate change the Arctic ice is melting, opening new possibilities for the economical use of the Arctic Ocean. However, the decision for shipping companies to transport freight through Arctic waters is based on many factors. The aim of the research is to develop a decision-supporting guidance for shipping companies. Methodology: Based on a literature review and subsequent validation through expert interviews, influencing factors are identified and classified using a framework covering Benefits, Opportunities, Costs, and Risks. A fuzzy set theory to structure multi-criteria decision problems is applied afterward. Findings: The results show that equipment, insurance, and inadequate port infrastructure are the factors with the highest influence in the Costs category and are the most influential factors overall. Security and market potential, the factors with the greatest impact on the Opportunities category, also rank highly as influential overall factors. The strongest Risk factors are weather conditions, delay, and collisions / accidents. The highest influence in the Benefits category are reduced costs. Originality: The influencing factors for Arctic freight shipping have so far only been considered in part with risks focus or other specific aspects, but not in the overall context. To consider multiple perspectives, 24 experts from different domains were involved.<br
CRIS-Team Scopus Importer:2024-12-16

Getting back into the swing of things: The adaptive path of purchasing and supply management in enhancing supply chain resilience - Küffner, Christoph; Münch, Christopher; Hähner, Sven; Hartmann, Evi (Journal of Purchasing and Supply Management, 2022)
The COVID-19 crisis posed significant challenges to global supply chains (SCs) and exposed their vulnerability to disruption. As SCs have evolved into complex structures comprising a multitude of globally dispersed companies that collaborate closely with one another, purchasing and supply management (PSM) have played a key role in addressing the crisis. The existing PSM measures for increasing supply chain resilience (SCRES) were stress tested and it became evident that these methods are applicable only to a limited extent due to their static perspective and their lack of a network character. Thus, this paper examines the role of PSM by identifying implemented response measures. By conducting 40 semi-structured interviews with experts from original equipment manufacturers and first-tier suppliers in the German automotive industry, a comprehensive overview of the industry was obtained. To reflect the network nature of the industry and the adaptive path of PSM, the data analysis is framed by resource dependence theory and the adaptive cycle approach theory. The results of the study are 25 response measures of PSM to enhance SCRES, categorized into three waves of measures: initial measures upon the occurrence of the disruption, temporary measures during the disruption, and post-disruption measures. In this way, the study contributes to the existing literature by demonstrating that PSM takes on a major role in increasing resilience by implementing diverse response measures. In addition, the study shows that PSM follows the path of an adaptive cycle, and that after the disruption and the initial and temporary measures, PSM adapts, which is reflected in the post-disruption measures. For practitioners, the study provides a list of response measures to increase resilience that can be used to review existing measures or implement new one
Keywords: Purchasing and supply management; Covid-19; Supply chain resilience; resource-dependency theory; adaptive cycle

Globales Netzwerkmanagement - Königsweg oder Irrglaube? - Jahns, Christopher; Hartmann, Evi (Die Automobilindustrie auf dem Weg zur globalen Netzwerkkompetenz, 2007)
WiSo-Import:2015-04-20:1257
Keywords: Innovation

Globale Spend Management Studie: Europäische Strategien für Low-Cost Country Sourcing - Jahns, Christopher; Hartmann, Evi; Lockström, M. (Wissenschaft & Praxis, 2005)
WiSo-Import:2015-04-13:1271

Global Purchasing Organizations: Towards Integrated Networks - Hartmann, Evi; Jahns, Christopher; Trautmann, Gerhard (18th North American Research/Teaching Symposium (NARS), 2007)
WiSo-Import:2015-04-17:1310
Keywords: Innovation

Global sourcing in integrated network structures: The case of hybrid purchasing organizations - Trautmann, Gerhard; Bals, Lydia; Hartmann, Evi (Journal of International Management, 2009)
An issue for companies in globally competitive markets is to adapt their organizational structures and governance in increasingly complex organizations. At the functional level of purchasing, companies are turning to hybrid purchasing organizations in order to leverage global sourcing benefits. One of the key challenges in this context is to distinguish between categories to be integrated across sites and those that are to remain under the authority of each purchasing location in order to maximize purchasing synergies. This paper presents a purchasing portfolio model that provides a comprehensive view of relevant global synergy dimensions. Based on a literature review, a theoretically-grounded purchasing portfolio model for global sourcing is developed. The theoretical basis stems from information processing theory, organizational buying behavior (OBB) and transaction cost economics. The validity of the model is explored by means of case study research. Complementing the extant literature, the theoretical contribution of the paper lies in not only addressing category selection criteria for exploiting economies of scale, but also for economies of information and learning and economies of process. Furthermore, it provides insights regarding integrated network coordination mechanisms at the functional level of purchasing.
WiSo-Import:2015-03-26:1018
Keywords: Purchasing; Portfolio model; Multinational corporations; MNCs; Integrated network structure; Hybrid organization; Global sourcing; Case study; Innovation

Global Sourcing Organization - Hartmann, Evi; Jahns, Christopher; Trautmann, Gerhard (69. Wissenschaftliche Jahrestagung des Verbandes der Hochschullehrer für Betriebswirtschaft e.V. (VHB), 2007)
WiSo-Import:2015-04-17:1311
Keywords: Innovation

Global Spend Management Survey: European Strategies for Low Cost Country Sourcing - Jahns, Christopher; Hartmann, Evi; Lockström, M. (Wissenschaft & Praxis, 2005)
WiSo-Import:2015-04-13:1272
Keywords: Innovation

Green and Lean? – Understanding ecological and environmental implications in the light of Industry 4.0 - Müller, Julian; Birkel, Hendrik; Veile, Johannes; Schmidt, Marie-Christin; Rücker, Marc; Hartmann, Evi; Voigt, Kai-Ingo (International Conference on Resource Sustainability (icRS) 2021, 2021)

Ground handling services at European hub airports: Development of a performance measurement system for benchmarking - Schmidberger, S.; Bals, Lydia; Hartmann, Evi; Jahn, C. (International Journal of Production Economics, 2009)
The liberalization of ground handling in Europe forces airports to assess their previous termperformancenext term relative to their competitors in order to remain competitive and sustain long-term competitive advantage. Together with main EU hub airports, action research was conducted for one year to develop previous termanext term holistic previous termperformance measurement systemnext term (PMS) for ramp services. The resulting PMS entails previous termanext term process-based perspective and reflects the supply chain of airport logistics. As the findings of an ex-post validation suggest, the previous termsystemnext term represents previous termanext term suitable basis for competitive benchmarking activities.
WiSo-Import:2015-03-26:1016
Keywords: Hub airports; Ground handling; European Union; Benchmarking; Action research; Innovation

Grün und sozial einkaufen: Nur so tun, als ob? - Foerstl, K.; Reuter, Carsten; Hartmann, Evi (Beschaffung aktuell, 2009)
Jedes Unternehmen will grün und sozial sein. Dabei nimmt der Einkauf eine maßgebliche Rolle ein. Tatsächlich? Oder tut er nur so?
WiSo-Import:2015-03-26:1232
Keywords: Innovation

How did supply chain networks handle the COVID-19 pandemic? Empirical evidence from an automotive case study - Spieske, Alexander; Gebhardt, Maximilian; Kopyto, Matthias; Birkel, Hendrik; Hartmann, Evi (International Journal of Physical Distribution & Logistics Management, 2022)
Purpose: The coronavirus disease 2019 (COVID-19) pandemic unveiled resilience deficits in supply chains. Scholars and practitioners aim to identify supply chain resilience (SCRES) measures suitable for this unique disruption; however, empirical evidence on a pandemic's specific characteristics, resulting challenges, and suitable countermeasures is scarce. Design/methodology/approach: A single-case study on an automotive supply chain network (ASCN), including eight nodes, was conducted. Based on current research and interviews with 35 experts, characteristic pandemic challenges for the ASCN were identified. Moreover, promising SCRES measures were determined along the most prominent SCRES levers. The findings lead to five central propositions and advance organizational information processing theory in the context of SCRES. Findings: This study’s results confirm unique pandemic characteristics along the supply chain disruption's duration, severity, propagation, and volatility. The resulting unprecedented challenges made the ASCN apply novel SCRES measures, particularly regarding collaboration and risk management culture. However, well-known visibility and flexibility strategies were also suitable. Overall, agility and collaboration measures showed the highest capacity to address characteristic pandemic challenges. A lack of preparedness impeded some measures' application, calling for enhanced proactive risk management following the pandemic. Originality/value: This paper addresses several research calls by providing in-depth empirical evidence on hitherto conceptually researched pandemic characteristics, challenges, and suitable SCRES measures from a network perspective. The study uncovers the different perceptions of individual tiers, emphasizing the need to analyze supply chain disruptions from multiple angles.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Automotive supply chain; Case study; COVID-19 pandemic; Organizational information processing theory; Supply chain network; Supply chain resilience

How digital transformation impacts organizational culture – A multi-hierarchical perspective on the manufacturing sector - Pfaff, Yuko; Wohlleber, Annika; Münch, Christopher; Küffner, Christoph; Hartmann, Evi (Computers & Industrial Engineering, 2023)
Digital transformation (DT) is not merely restricted to a company's adoption of digital technologies. Still, it implies changes to a company's business model, strategies, and culture. However, the impacts of DT on organizational culture (OC) have not been widely researched yet. Cultural dimensions have not been analyzed in the context of the digital age, neglecting the fact that the current OC needs to transform into a digital OC. Consequently, this paper contributes by identifying the main challenges of a company's transformation and examining the dynamics of the OC dimensions in the digital context. By applying adaptive structuration theory and an input-process-output model, this study provides an overview of the transformation of a manufacturing company's OC from five years ago until now and five years in the future as a result of its DT program in a single case study. The main findings are that DT transforms the company's OC toward increased collectivism, femininity, indulgence, and long-term orientation and reduces power distance and uncertainty avoidance.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Digital organizational culture; Digital transformation; Manufacturing; Multi-hierarchical; Single case study

How Organizations Prepare for the Future: A Comparative Study of Firm Size and Industry - Meyer, Tobias; von der Gracht, Heiko A.; Hartmann, Evi (IEEE Transactions on Engineering Management, 2020)
The question of how companies can best prepare for the future to maintain or improve their existing position in the market place has increased its momentum. This article aims to analyze future preparedness as a joint construct consisting of a company's exploitation and exploration capabilities. In this article, we thereby consider exploitation as a firm's strategy to prepare for the future by focusing on its organizational structure and resources, and exploration as its strategy to engage in corporate foresight to anticipate changes in their environment. Previous scholars centered their research on large companies and single industries. In this article, we close this gap by analyzing future preparedness of large companies as well as of small and medium-sized enterprises from 12 different industries. Data were obtained from a heterogeneous sample of 602 companies of the German economy. For data analysis, the measured variables were classified using principal component analysis and compared by means of variance analysis. Our results indicate that companies rather build on exploitation of internal resources than on exploration of their environment. We further present firm size and industry as predictors for future preparedness strategies and found that the scope of future preparedness augments with firm size.<br
Keywords: (Ambidexterity; comparative study; corporate foresight; factor analysis; future preparedness; managerial survey; small and medium-sized enterprise (SMEs); )

Human Resource Management Issues in Supply Chain Management Research: A Systematic Literature Review from 1998 to 2014 - Hohenstein, Nils Ole; Feisel, Edda; Hartmann, Evi (International Journal of Physical Distribution & Logistics Management, 2014)

Identifying and developing purchasing professionals for the future: A Longitudinal Case Study - Feisel, Edda; Hartmann, Evi; Jahns, Christopher (17th International Purchasing & Supply Education & Research Association (IPSERA), 2008)
WiSo-Import:2015-04-17:1293
Keywords: Innovation

Impact of institutional coordination on national entrepreneurship: A conceptual framework - Clark, K.; Rättich, Gordian; Hartmann, Evi (Academy of International Business Annual Meeting, 2011)
WiSo-Import:2015-04-17:3120

Impact of IoT challenges and risks for SCM - Birkel, Hendrik; Hartmann, Evi (Supply Chain Management-An International Journal, 2019)
Purpose The purpose of this paper is to offer a comprehensive overview of challenges and risks of the Internet of Things (IoT) in supply chain management (SCM) and provide a structured framework for classifying and analyzing the relevant literature to deduce insights for research and practice. Design/methodology/approach A systematic literature review (SLR) of 102 peer-reviewed journal articles on the topic of IoT in SCM was conducted. Findings This review identifies, categorizes and describes the relevant literature regarding the dimensions time and specificity. The resulting framework contains a holistic overview including focus areas and relations of macro-environmental, network-related and organizational challenges and risks. Furthermore, this review represents a conceptual framework for future research, considering the multidisciplinary body of the subject and provides an analysis of the timeline of literature, journals and used methodologies. Practical implications This study offers valuable insights into IoT and its impact on applications, processes and the structure of organizations and supply chains (SCs). The identification of challenges and risks helps to prepare for changes in the future because of the disruptive nature of this technology. Originality/value The originality of this paper lies in the synthesis of the fragmented body of literature of IoT challenges and risks for SCM. The derived framework and identification of relations and research gaps provide the foundation for further research to evaluate the relations between challenges and risks and offer solutions.
Keywords: Supply Chain Management; Supply risk; Internet of Things; IoT; Systematic literature review

Implementing Global Sourcing through Innovative Procurement Organizations - Hartmann, Evi; Trautmann, Gerhard (Innovation Management in Global Networks - A Challenge and Chance for Top-Management, 2006)
WiSo-Import:2015-04-20:1264
Keywords: Innovation

Implementing Global Sourcing Through Purchasing Portfolio Management - Trautmann, Gerhard; Bals, Lydia; Hartmann, Evi (9th Annual International Business Research Forum, 2008)
WiSo-Import:2015-04-17:1301
Keywords: Innovation

Implementing measures for performance improvement in purchasing marketing services – developing a step-wise approach - Bals, Lydia; Hartmann, Evi (18th North American Research/Teaching Symposium (NARS), 2007)
WiSo-Import:2015-04-17:1303
Keywords: Innovation

Implementing Vital Dynamic Capabilities to Succeed in Digital Transformation: A Multiple-Case Study in Maritime Container Shipping - Wohlleber, Annika; Bock, Maximilian; Birkel, Hendrik; Hartmann, Evi (IEEE Transactions on Engineering Management, 2022)
Dynamic capabilities (DCs) were found to be a success factor in maritime container shipping (MCS) regarding the volatile future, leading to competitive advantages in digital transformation (DT) efforts. Despite its relevance, it remains unclear which DCs are vital for incumbent maritime organizations to succeed in DT and how DCs need to be implemented to enable DT. Referring to this research gap, this article is the first to empirically classify digital sensing, seizing, and transforming capabilities and uncover antecedents relevant to these capabilities. Thereby, we initially combine the DCs view with DT efforts in MCS, providing valuable insights for decision-makers in port authorities, carriers, and freight forwarders. Answers were sought through a cross-case analysis involving 26 experts along the maritime supply chain. The findings highlight strategic agility, innovation ecosystems, and the redesign of organizational structures the most vital second-order concepts for succeeding in DT in MCS. Implementing the identified DCs in MCS is of considerable strategic relevance, advancing the transformation of MCS into a digitalized, efficient, and sustainable industry that preliminary provides service-based offers to its customers. Consequently, this article presents a strategic basis for adapting DT roadmaps and investments in MCS, preparing incumbent MCS organizations for the digital future.
CRIS-Team WoS Importer:2022-09-23
Keywords: Container; digital seizing; digital sensing; digital transforming; digitalization; dynamic capabilities (DCs); freight transportation; maritime

Implications of Industry 4.0 implementations on Supply Chain Governance – an interorganizational multi-tier perspective - Pfaff, Yuko; Birkel, Hendrik; Hartmann, Evi (Proceedings of the Annual International Purchasing & Supply Education & Research Association (IPSERA) Online Conference 2021, 2021)

Improved Purchasing Performance through Measurement and Development of Purchasing Skills - Feisel, Edda; Hartmann, Evi; Schober, Holger (23rd Industrial Marketing and Purchasing (IMP) conference, 2007)
WiSo-Import:2015-04-17:1307
Keywords: Innovation

Improving supply chain risk management: Implications for process transformation and global procurement markets via the Internet of Things - Birkel, Hendrik; Hartmann, Evi (Proceedings of the Annual International Purchasing & Supply Education & Research Association (IPSERA) Conference, 2019)
The severity of potential risks of today’s global networks emphasizes the need for supply chain risk management (SCRM), to design economically competitive supply chains and pro-vide competitive advantage. The internet of things (IoT) offers the opportunity for a radical change through increasing transparency due to the interconnection of partners, goods and pro-cesses. We contribute to this field by conducting a multiple case study, examining how IoT influences SCRM. Our results show IoT positively influences the risk identification, assess-ment, treatment and monitoring, and improves the external pathway of SCRM. However, the application focuses on few use cases, which entail several barriers.<br
Keywords: Supply chain risk management; Internet of Things; IoT; Supply chain transparency; Digitalisation

Industry 4.0 technologies as enablers of collaboration in circular supply chains: a systematic literature review - Gebhardt, Maximilian; Kopyto, Matthias; Birkel, Hendrik; Hartmann, Evi (International Journal of Production Research, 2021)
Close and novel forms of collaboration among supply chain stakeholders within and beyond industry boundaries are essential for implementing a circular economy. Industry 4.0 technologies, as recognised enablers for circular systems, can support such collaboration. This study explores the intersection of the circular economy, supply chain collaboration, and Industry 4.0. First, we derive an analytical framework that contextualises circular supply chain collaboration. Second, based on this framework, we conduct a systematic literature review that explores how Industry 4.0 technologies can enable collaboration mechanisms. The review shows that information sharing and joint planning and decision-making are the most common collaboration mechanisms studied. Simultaneously, the Internet of Things, Blockchain, and Cloud Systems are the most discussed technologies to enable those mechanisms. The most prominent review sample patterns are synthesised into three archetypes for Industry 4.0-enabled circular supply chain collaboration. Furthermore, the study derives nine promising questions for future research along six main dimensions: Digital Twins and Artificial Intelligence, joint knowledge creation and innovation, collaboration in product design and planning, systemic collaboration across industry boundaries, contextualisation with barriers for implementing circular supply chains, and transferability of applications across industries.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Circular economy; collaboration; digital technology; industry 4.0; supply chain management

Influence of different stakeholders on first-tier suppliers’ sustainable supplier selection: insights from a multiple case study in the automotive first-tier industry - Lechler, Sabrina; Canzaniello, Angelo; Wetzstein, Anton; Hartmann, Evi (Business Research, 2019)
Public and academic attention towards sustainably managing companies and corresponding supply chains has been gaining significant momentum in recent years. While extensive literature is available on corporate sustainability and the original equipment manufacturers’ (OEMs) downstream supply chains, there is little empirical knowledge concerning why first-tier (FT) suppliers in the upstream supply chain implement sustainability into their supplier selection (SS) processes. However, FT suppliers have a crucial role in ensuring sustainability in upstream supply chains, as they are a key transmitter and often accountable for their OEMs’ sub-supplier portfolios. Grounded on a cross-case study approach of five FT suppliers, two associations and three non-governmental organizations (NGOs) as well as stakeholder theory, this paper investigates how different stakeholder groups are influencing the integration of sustainability aspects into FT suppliers’ SS processes. Therefore, government, NGOs, OEMs and employees are investigated as stakeholder groups. Characteristics, such as FT suppliers’ size, legal structure, material criticality, employees’ distance to the supply chain function, company culture and industry culture, could be identified as factors that influence the urgency of stakeholders’ sustainability claims and thus FT suppliers’ perceived sustainability pressure. Moreover, with regard to the OEM stakeholder group, it was found that, depending on the urgency of OEMs’ sustainability claims, FT suppliers align their sustainable SS processes to the actions and expectations of different stakeholder groups and thus fulfill the OEM’s sustainability expectations to varying degrees. Thus, our study contributes empirical knowledge to this so far underrepresented research field and is moreover beneficial for decision makers.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Case study research; First-tier supplier; Stakeholder theory; Supplier management; Sustainable supplier selection

Innovationen fördern und gleichzeitig Kosten senken? - Hartmann, Evi; Moser, Roger; Weidmann, Markus (Beschaffung aktuell, 2007)
Als Methodik zur Innovationsförderung und Kostensenkung während der gesamten Laufzeit von Produkten und Dienstleistungen wird die Wertanalyse heute durch den Einkauf wiederentdeckt.
WiSo-Import:2015-03-26:1238
Keywords: Innovation

Integration and Coordination in Purchasing and Supply Management: Their Antecedence and Effects on Purchasing and Firm Performance - Foerstl, K.; Hartmann, Evi; Wynstra, F.; Moser, Roger (71. Wissenschaftliche Jahrestagung des Verbandes der Hochschullehrer für Betriebswirtschaft e. V. (VHB), 2009)
WiSo-Import:2015-04-17:1286
Keywords: Innovation

Integration in Hybrid Global Sourcing Organizations - Hartmann, Evi; Trautmann, Gerhard; Turkulainen, Virpi (18th Annual Conference of the Production and Operations Management Society (POMS), 2007)
WiSo-Import:2015-04-17:1313
Keywords: Innovation

Integration in the global sourcing organization–an information processing perspective - Trautmann, Gerhard; Turkulainen, Virpi; Hartmann, Evi; Bals, Lydia (Journal of Supply Chain Management, 2009)
Global sourcing refers to the integration of decision making across worldwide purchasing units within a multinational corporation (MNC). In order to manage the integration challenge, firms have a number of tools, varying from centralization and formalization to cross-locational teams. In this paper, we focus on explaining how and why to integrate in different circumstances. The aim of this paper is to complement prior research on global sourcing organizations, which is still rather scarce and more exploratory in nature. By extending the arguments of the information processing perspective of organizations to the global sourcing context, we seek to propel a theoretical discussion on integration in the global sourcing organization. Based on the results of 12 case studies in three MNCs, we propose that integration approaches in global sourcing organizations vary depending on the three contingencies of category characteristics, supply environment characteristics and interdependence of the purchasing units.
WiSo-Import:2015-03-26:1019
Keywords: organization; international/global purchasing; case studies; Innovation

Interconnectedness of actor bonds in service triads – a social capital perspective - Hartmann, Evi; Herb, Stefan (Industrial Marketing Management, 2015)

Internal Customer Orientation in Purchasing & Supply Management - Learning from Key Account Management - - Reinhardt, S.; Hartmann, Evi; Jahns, Christopher (23rd Industrial Marketing and Purchasing (IMP) conference, 2007)
WiSo-Import:2015-04-17:1316
Keywords: Innovation

Internal Key Account Management in PSM - An Empirical Analysis - Reinhardt, S.; Hartmann, Evi; Kaiser, Gernot (Academy of Management Annual Meeting, 2010)
WiSo-Import:2015-04-17:1283
Keywords: Innovation

Internet-based E-markets as a meta-enterprise information system - Grieger, Martin; Hartmann, Evi; Entchelmeier, Aiko (Encyclopedia of Networked and Virtual Organizations, 2006)
Due to the reduction of the degree of value added within many companies, purchasing and supply management has been acknowledged as an important lever for corporate performance enhancement. Recent research has shown that the installation of performance measurement systems in purchasing and supply management is a decisive management tool for purchasing and supply management. Based on the old saying “you can’t manage what you can’t measure” companies must have decisive metrics that translate supply strategy into action and drive company performance. The paper applies selected management theories to the research field and suggests a framework for the design, implementation and enablement of performance measurement in purchasing and supply management.
WiSo-Import:2015-04-20:1261
Keywords: Innovation

Internet of Things – the future of managing supply chain risks - Birkel, Hendrik; Hartmann, Evi (Supply Chain Management-An International Journal, 2020)
Purpose: The purpose of this paper is to investigate the implications for supply chain risk management (SCRM) by applying internet of things (IoT). Therefore, the impact and effects on the SCRM process, as well as the internal and external pathway and the outcome of SCRM are examined. Design/methodology/approach: This study adopts a multiple case study methodology with twelve companies from the manufacturing industry. This study is guided by the information processing theory (IPT) and a theory-grounded research framework to provide insights into information requirements and information processing capabilities for IoT-supported SCRM. Findings: The studied cases demonstrate an increase in data availability in the companies that contribute to improved process transparency and process management. Furthermore, the process steps, risk transparency, risk knowledge and risk strategies have been enhanced, which enabled improved SCRM performance by fitting information requirements and information processing capabilities, thus allowing for competitive advantage. Practical implications: This study offers in-depth insights for SCRM managers into the structure of IoT systems, primary use cases and changes for the process itself. Furthermore, implications for employees, incentives and barriers are identified, which could be used to redesign SCRM. Originality/value: This study addresses the requirement for additional empirical research on technology-enhanced SCRM, supported by IPT as a theoretical foundation. The radical change of SCRM by IoT is demonstrated while discussing the human role, implications for SCRM strategies and identifying relevant topics for future development.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Case Studies; Collaboration; Information processing theory; Internet of things; IoT; New technology; RFID Technology; Risk Management; Supply Chain disruptions; Supply chain risk management; Supply risk

Inter-organizational network structures in Russia - An institution-based and social-embeddedness view, Organisational Change and Development in Transitional Countries - Weigl, T.; Hartmann, Evi; Darkow, Inga-Lena (The European Institute for Advanced Studies in Management (EIASM), 2006)
WiSo-Import:2015-04-17:1332
Keywords: Innovation

Inter-organizational network structures in Russia: organizational changes from institutional and social embeddedness perspectives - Weigl, T.; Jahns, Christopher; Hartmann, Evi; Darkow, Inga-Lena (Human Resource Development International, 2008)
Theory posits that organizations are embedded socially within their environment. The level of embeddedness depends highly on the environmental uncertainty a company and its network partners face. The latest research on transition economies indicates that the institutional framework in these countries is highly relevant for inter-organizational structures (i.e. formalization, standardization, frequency, intensity and reciprocity). As Russia constitutes a good example of high environmental uncertainty, a closer look at organizational changes in general and inter-organizational network structures in particular is taken. This paper extends the theoretical and empirical scope of social and economic theories on inter-organizational structures by formulating a conceptual framework that unites economic rationalism with socially embedded arguments. Contributing to emerging international HRD literature, the objective is to understand better the institutional influences on network structures and thus on organizational change. Moreover, it will be demonstrated how far organizational changes and human resource development is associated with institutional influences on network structures.
WiSo-Import:2015-03-26:1226
Keywords: Russia; organization change; networks; international HRD; institutional perspectives; Innovation

Intra-industry strategic alliances for managing sustainability-related supplier risks: Motivation and outcome. - Canzaniello, Angelo; Fifka, Matthias; Hartmann, Evi (International Journal of Physical Distribution & Logistics Management, 2017)
Purpose The purpose of this paper is to explore how intra-industry strategic alliances (SAs) seek to assess supplier risk related to sustainability, what motivation drives single members to form or join such an SA, and how such a joint endeavor affects supplier risk management. Design/methodology/approach An embedded single case study with multiple units of analysis was conducted. The main data were collected through semi-structured interviews with key respondents from seven leading chemical companies, three of which were founding members of the SA, while four were new members. Findings This paper shows that forming/joining an SA concerning sustainability-related supplier risk assessment, results in the reduction of task uncertainty and equivocality as well as the increase of information processing capacities. Based on the implemented sharing routines, a higher overall efficiency can be achieved. Moreover, the members benefit from an enhanced identification of varying stakeholder expectations, a facilitated capability building and a more comprehensive supplier risk assessment. In particular, the joint endeavors result in assessment processes of higher robustness, which provide outcomes of higher quality. Originality/value This paper is the first to investigate companies’ efforts toward improving their supplier risk management in the area of sustainability by establishing/joining an intra-industry SA. By providing insights into the motivation to form or join such a collaborative platform and illustrating the effects that arise from the SA’s work from an organizational information processing perspective, it provides a contribution to both academics and managerial practice. Purpose The purpose of this paper is to explore how intra-industry strategic alliances (SAs) seek to assess supplier risk related to sustainability, what motivation drives single members to form or join such an SA, and how such a joint endeavor affects supplier risk management. Design/methodology/approach An embedded single case study with multiple units of analysis was conducted. The main data were collected through semi-structured interviews with key respondents from seven leading chemical companies, three of which were founding members of the SA, while four were new members. Findings This paper shows that forming/joining an SA concerning sustainability-related supplier risk assessment, results in the reduction of task uncertainty and equivocality as well as the increase of information processing capacities. Based on the implemented sharing routines, a higher overall efficiency can be achieved. Moreover, the members benefit from an enhanced identification of varying stakeholder expectations, a facilitated capability building and a more comprehensive supplier risk assessment. In particular, the joint endeavors result in assessment processes of higher robustness, which provide outcomes of higher quality. Originality/value This paper is the first to investigate companies’ efforts toward improving their supplier risk management in the area of sustainability by establishing/joining an intra-industry SA. By providing insights into the motivation to form or join such a collaborative platform and illustrating the effects that arise from the SA’s work from an organizational information processing perspective, it provides a contribution to both academics and managerial practice.
Keywords: Sustainability; Organizational information processing theory; Case study; Strategic alliance; Strategic collaboration; Supplier assessment; Supplier risk management; Sustainability standard

Investigating the Human Factor in SCM: A Systematic Citation Network Review from 1998 to 2018 - Kopyto, Matthias; Feisel, Edda; Giunipero, Larry; Hartmann, Evi (Academy of Management Proceedings, 2019)

Is quality still free?: Empirical evidence on quality cost in modern manufacturing - Plewa, Markus; Kaiser, Gernot; Hartmann, Evi (International Journal of Quality and Reliability Management, 2016)
Purpose The purpose of this paper is to provide empirical evidence for competing representations of the prevention-appraisal-failure model of quality cost. Design/methodology/approach The authors conduct regression analysis on a secondary data set to reveal relationships among total cost of quality, its components and overall quality performance. Findings Total cost of quality and its failure cost component are significantly lower at higher levels of quality, while the prevention and appraisal cost components are not observed to be significantly higher at higher levels of quality. The authors propose a modification to the modern representation of the prevention-appraisal-failure model. Practical implications In manufacturing, ever higher levels of quality are associated with significantly lower quality cost. Originality/value Using a large, unique data set for secondary analysis, combined with employing a high-level measure for overall quality performance, the authors provide evidence for the aggregate explanatory power of prevalent representations of the prevention-appraisal-failure cost of quality mode
Keywords: Manufacturing; Quality management; Quality costs; Secondary data analysis

Konzepte, Grundlagen und Herausforderungen im Management globaler Wertschöpfungsketten - Birkel, Hendrik; Hartmann, Evi (Handbuch Globale Kompetenz, 2021)
Die Globalisierung erhöht die Komplexität heutiger Wertschöpfungsnetzwerke zunehmend und erschwert dadurch dessen Management. Dieser Beitrag beschäftigt sich daher mit den grundlegenden Konzepten, Strategien und zukünftigen Handlungsfeldern im Kontext der Globalisierung. Dabei wird insbesondere auf die Unterteilung und das Management globaler Supply Chains, Herausforderungen durch die Globalisierung sowie Globalisierungsstrategien eingegangen und deren Vor- und Nachteile diskutiert. Darüber hinaus wird der Einfluss von Technologien wie dem Internet of Things, Big Data Analytics und Künstlicher Intelligenz, sowie zukünftige Entwicklungen im Rahmen der Nachhaltigkeit aufgezeigt. Denn in Zukunft werden Unternehmen nicht ökonomisch, sondern auch ökologisch und sozial agieren müssen und sich selbst und ihre Mitarbeitenden darauf vorbereiten.
Keywords: Supply Chain Management; Globalisierung; Globalisierungsstrategien; Trends und Technologien; Kompetenzen der Mitarbeitenden

Lateral transshipments: An institutional theory perspective - Stanger, Sebastian; Wilding, Richard; Yates, Nicola; Cotton, Sue; Hartmann, Evi (International Journal of Physical Distribution & Logistics Management, 2013)
Purpose: Are lateral transshipments an effective instrument to ensure the safe and efficient supply of blood? This paper will use the lens of institutional theory to determine how the blood supply chain can benefit from lateral transshipments and what requirements are necessary for their implementation. The paper aims to discuss these issues. Design/methodology/approach: The research design comprises two stages. First, 16 case studies clustered into two case groups were conducted with transfusion laboratories in UK hospitals resulting in the derivation of eight key themes which were tested using a follow-up survey. Findings: The blood supply chain acts under the influence of significant institutional pressures. Coercive pressures result from regulations enforced to ensure the safe supply of blood, normative pressures are imposed by society, demanding wastage is minimized and mimetic pressure from other hospitals fosters efficient supply chain operation. Lateral transshipments offer a powerful organizational tool to allow the blood supply chain to conform to these pressures. Research limitations/implications: This paper offers a novel institutional perspective on a complex supply chain issue where additional external pressures are seen to complicate the context. Due to the special characteristics of the blood supply chain, generalization of the findings to other industries must be done with care. Practical implications: The paper confirms the benefits of lateral transshipments in a perishable product context. Special requirements for the blood supply chain/health care services are identified. Originality/value: The key contributions of this paper are five propositions which offer an institutional theory perspective on the application of lateral transshipment relationships in the blood supply chain. © Emerald Group Publishing Limited.
WiSo-Import:2015-03-26:4751
Keywords: Blood; Case study; Horizontal collaboration; Institutional theory; Inventory pooling; Stock sharing; Supply chain management

Linking Corporate Entrepreneurship and Supply Chain Resilience to strengthen Business Performance: An Empirical Analysis - Sturm, Sebastian; Hohenstein, Nils-Ole; Hartmann, Evi (Proceedings of the Annual International Purchasing & Supply Education & Research Association (IPSERA) Conference 2022, 2022)
Supply chain resilience (SCRES) has become a promising approach to ensure a proper ﬂow of goods and materials in the presence of increasing complexity, uncertainty and vulnerability of globe-spanning supply chains. The antecedents and drivers of SCRES, and especially cross-disciplinary relationships, however, still represent a gap in the field of supply chain management research. Therefore, in line with the IPSERA 2022 conference theme to build bridges rather than walls, this paper connects two distinct but related, previously unconnected research fields within the conference stream of supply chain risk and resilience. More precisely, this empirically validated study combines research on corporate entrepreneurship (CE) and SCRES to better explain how to achieve competitive advantage in changing market conditions. Thus, this discipline-bridging paper examines the following research question to enhance the understanding of supply chain interrelationships: How does corporate entrepreneurship affect a company’s degree of supply chain resilience and thereby the ability to achieve superior business performance in dynamic environments? To answer this question, the authors conduct a review on CE and SCRES literature. In this context, CE aims to create an entrepreneurial orientation within existing firms that can be characterized as a multidimensional construct of innovativeness, proactiveness, risk-taking, autonomy and competitive aggressiveness. CE is assumed to be a key enabler of competitive advantage by identifying, implementing and encouraging new and innovative ways to cope with environmental uncertainty. At the same time, SCRES has been widely acknowledged to positively influence business performance (BP) in dynamic and competitive landscapes and in case of unexpected supply chain disruptions. Hence, we develop a model that combines CE and SCRES to analyze its relationships and influence on BP involving both financial and broader commercial criteria. It is investigated whether entrepreneurial activities inject new and innovative responses to disruptive supply chain events and create new sources of competitive advantage. To provide evidence for the hypothesized relationships between CE, SCRES and BP, the conceptual model is validated with empirical data. For this purpose, the authors conduct a survey and apply structural equation modeling on data collected from more than 100 international companies operating in a diverse range of industries. We find significant path coefficients for all hypothesized relationships. Therefore, we find support for the hypotheses that appropriate CE initiatives strengthen SCRES and foster BP. These results can encourage practitioners to pursue entrepreneurial activities to mitigate disturbances by enhancing SCRES, recover from disruptions faster than competitors, and ultimately improve BP. From a theoretical point of view, this paper advances CE and SCRES research by combining two different research streams to provide new insights about the interrelationships and facilitate innovative supply chain managemen

Linking entrepreneurial orientation and supply chain resilience to strengthen business performance: an empirical analysis - Sturm, Sebastian; Hohenstein, Nils-Ole; Hartmann, Evi (International Journal of Operations & Production Management, 2023)
PurposeThis study examines the interactions between entrepreneurial orientation, supply chain resilience (SCRES) as well as the financial and commercial dimensions of business performance.Design/methodology/approachDrawing on a literature review, the authors develop a research model to identify positive relationships between five specific dimensions of entrepreneurial orientation, SCRES and business performance based on the dynamic capabilities view. The hypotheses are then empirically validated by applying partial least squares structural equation modeling (PLS-SEM) on survey data obtained from a questionnaire and 168 global companies.FindingsThe results partially support the hypotheses and suggest that entrepreneurial activities complement the resilience of supply chains to sudden disruptions and therefore also foster competitive advantage.Originality/valueThe relationships between entrepreneurial orientation, SCRES and business performance are examined and validated empirically in a single model, bridging the gap between these distinct research streams and shedding further light on supply chain risk management.
CRIS-Team WoS Importer:2023-02-10

Logistics & Supply Chain Management. Highlights and Hot Spots - Jahns, Christopher; Darkow, Inga-Lena; Hartmann, Evi; Schober, Holger; Walter, S. (Wissenschaft & Praxis, 2006)
WiSo-Import:2015-04-13:1265
Keywords: Innovation

Long-run dynamics between cost of quality and quality performance - Sturm, Sebastian; Kaiser, Gernot; Hartmann, Evi (International Journal of Quality and Reliability Management, 2019)
Purpose: The dynamics of quality performance and quality cost are gaining renewed interest in quality management literature. Using large sample secondary data, the purpose of this paper is to build up empirical evidence for increasing quality performance in manufacturing in the long-run. The authors then examine whether it is possible to reduce internal and external failure cost over time without increasing prevention and appraisal expenditures in return. Finally, a scale effect in reducing quality cost is measured to clarify the long-run dynamics between quality cost and quality performance. Design/methodology/approach: The authors conduct statistical analysis on a large sample secondary data set to reveal relationships between total cost of quality, its components and overall quality performance. Findings: Significantly higher quality performance and lower quality cost are observed in the long-run. Quality costs grow less than half as fast as sales volume, pointing to a significant scale effect in quality cost reduction. Practical implications: Businesses can use these implications for targeting failure costs and budgeting appraisal and prevention costs. Based on company-specific historical learning behavior through prevention and appraisal activities, an increasingly reliable prognosis of failure cost shall be possible. Originality/value: For the first time, quality performance and cost dynamics are assessed using a secondary data set with more than 400 observations. A scale effect for quality cost reduction is measured. The results are of great importance to quality management practice and research.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Manufacturing strategy; Operations management; Production economics; Quality costing; Quality management

Low-Cost Country Sourcing - Opportunity or Necessity? - Hartmann, Evi; Lockström, M.; Reuter, Carsten (24. Deutscher Logistik Kongress: Effizienz-Verantwortung-Erfolg, 2007)
WiSo-Import:2015-04-20:1256
Keywords: Innovation

Management of the Innovation Process: A Comparison of Theoretical and Practical Approaches - Bals, Lydia; Hartmann, Evi; Gruner, Jean Raoul (Produkt- und Prozessinnovationen in Wertschöpfungsketten, 2008)
The implementation and management of technology and innovation processes increasingly gain importance due to fierce competition and continuously changing environmental conditions on world markets. Facing its realization, theory and practice have not yet unanimously agreed on how to efficiently and effectively manage innovation processes. Based on a theoretical framework about different innovation types and strategies, four operational aspects of implementing and managing innovation processes are introduced and systematically compared with corresponding practices of an international elevator/escalator engineering company. The article concludes that the selected company provides an example of best-practice management of innovation processes.
WiSo-Import:2015-04-20:1250
Keywords: Innovation

Management of the Innovation Process: A Comparison of Theoretical and Practical Approaches - Hartmann, Evi; Bals, Lydia; Gruner, Jean Raoul (Herbsttagung der Wissenschaftlichen Kommission Produktionswirtschaft des Verbands der Hochschullehrer für Betriebswirtschaft e.V. 2007, 2007)
WiSo-Import:2015-04-17:1308
Keywords: Innovation

Managing supplier sustainability risks in a dynamically changing environment—Sustainable supplier management in the chemical industry - Foerstl, K.; Reuter, Carsten; Hartmann, Evi; Blome, Constantin (Journal of Purchasing and Supply Management, 2010)
Varying definitions and interpretations of sustainability standards have become a major concern for purchasing and supply management (PSM). As the foremost interface to an increasingly global supply base, PSM plays an important role in the mitigation of sustainability-related risks. By conducting responsible purchasing and supplier management, the risk of corporate reputational damage to the buying firm, caused by supplier misconduct, can be avoided. However, resources for effective risk-mitigation are limited and the applicability of supply risk assessment and supplier assessment methods have not been evaluated for sustainability. In this paper, we explore how leading PSM functions identify, assess, and treat supplier sustainability risks and elaborate on the integration of sustainability risk management in supplier management processes. Based on the findings from a multiple case study in the chemical industry and by drawing on the dynamic capabilities view (DCV), we propose that mature and sustainable supplier management capabilities are a source of competitive advantage in terms of lower exposure to reputational risks and enhanced operational performance. © 2010 Elsevier Ltd. All rights reserved.
WiSo-Import:2015-03-26:3116
Keywords: Corporate social responsibility; Supplier management; Supply risk management; Sustainability

Managing Supply Chain Risk - A Supply-Side Perspective - Kern, Daniel; Moser, Roger; Hartmann, Evi; Moder, Marco (2010)
WiSo-Import:2015-04-17:1277
Keywords: Innovation

Mapping the intellectual foundation of low-carbon supply chains: A theory-based literature review on buyer-supplier relationships - Steiner, Benedikt; Münch, Christopher; Küffner, Christoph; Hartmann, Evi (Journal of Cleaner Production, 2023)
Over the past two decades, researchers have investigated buyer-supplier relationships (BSRs) to foster supply chain decarbonization as a countermeasure to the effects of climate change. However, the academic intellectual foundation is still far from maturing, not only because of its novelty but also because scholars have focused on narrow topics and theoretical lenses. Thus, this paper aims to understand the present intellectual structure of BSRs in low-carbon supply chains (LCSCs) while showing the lack of knowledge and the need to investigate research topics through multiple theoretical lenses. In this study, a literature review was conducted by collecting data without date restriction in July 2023 and analyzing 804 peer-reviewed articles from top-ranked academic journals. Both quantitative and qualitative methods were applied for the paper's content analysis, including a multiple correspondence analysis and a homogeneity analysis of variance by means of alternating least squares (HOMALS) to map the data. The results show a high degree of fragmentation within the present theoretical foundation of BSRs in LCSCs, including a limited application of theoretical lenses and the need for a balanced research agenda. Based on the assessment of the existent literature, 29 research propositions are presented and they are categorized under eight theoretical lenses that constitute the interpretive framework. This study contributes to building theoretical knowledge of supply chain management 1) by analyzing the present intellectual foundation while mapping investigated research topics and theories in a two-dimensional graph and 2) by proposing a balanced research agenda with 29 research propositions to develop the field of BSRs in LCSCs. In addition to the method's originality in the mentioned field, this review highlights emerging research topics.

Marketing as an internal client of purchasing – Exploring meaningful Marketing/Purchasing interaction - Bals, Lydia; Hartmann, Evi; Ritter, Thomas (23rd Industrial Marketing and Purchasing (IMP) conference, 2007)
WiSo-Import:2015-04-17:1305
Keywords: Innovation

Marketingdienstleistungen - Unantastbare Kompetenz des Marketing? Ein Lagebericht zur Beschaffung von Marketingdienstleistungen, Teil 1 - Jahns, Christopher; Hartmann, Evi; Wagner, A. (Beschaffung aktuell, 2006)
Kosteneinsparungen von bis zu 40 Prozent werden prognostiziert, wenn das Supply Management bei der Beschaffung von Marketingdienstleistungen einbezogen wird. Angesichts solcher Aussichten rückt das Thema verstärkt in den Fokus des Top Managements und damit auch in das Interesse der Praxis und Forschung des Supply Managements.
WiSo-Import:2015-03-26:1244
Keywords: Innovation

Marketing Spend Survey - Jahns, Christopher; Hartmann, Evi; Wagner, Anja (Wissenschaft & Praxis, 2005)
Der Einkauf von Marketingdienstleistungen birgt bedeutende Optimierungspotenziale. Welche Organisationsformen und Prozesse gewählt werden sind ebenso Gegenstand der Analyse wie branchen- und länderspezifische Besonderheiten und Gestaltungsempfehlungen für die erfolgreiche Zusammenarbeit von Einkauf, Supply Management und Marketing.
WiSo-Import:2015-04-13:1273
Keywords: Innovation

Maximizing impact of investments into purchasing and supply management - Hartmann, Evi; Kerkfeld, Dieter (International Journal of Physical Distribution & Logistics Management, 2012)
WiSo-Import:2015-03-26:4547

Nachhaltige Lieferketten durch KI - Münch, Christopher; Küffner, Christoph; Hartmann, Evi (Jahrbuch Logistik 2023, 2023)
Nachhaltigkeit gilt heutzutage als ein wichtiger Bestandteil der Geschäftstätigkeiten von Unternehmen. Dennoch stoßen bisherige Ansätze zum Management von Nachhaltigkeit aufgrund immer komplexerer und diversifizierterer Lieferketten an ihre Grenzen. Das Sammeln und Analysieren von nachhaltigkeitsbezogenen Daten sowie die Ableitung von Maßnahmen bei Nachhaltigkeitsverstößen sind durch den Menschen kaum noch zu realisieren. An dieser Stelle kann künstliche Intelligenz (KI) ansetzen und den Umgang mit Nachhaltigkeit in Lieferketten automatisieren. Der vorliegende Beitrag thematisiert die Anwendung von KI zur Erhöhung der Nachhaltigkeit in Lieferketten und zeigt dabei mögliche Anwendungsgebiete auf.<br

No Vehicle Means No Aid—A Paradigm Change for the Humanitarian Logistics Business Model - Hirschinger, Micha; Moser, Roger; Schaefers, Tobias; Hartmann, Evi (Thunderbird International Business Review, 2015)
The growing interest in humanitarian logistics is witnessed by an increasing focus of researchers and practitioners on that topic. Transportation in particular is emphasized as key to disaster relief. Despite its relevance, it suffers from a number of drawbacks creating inefficiencies and limited effectiveness of aid. This article describes a paradigm change for fleet management in humanitarian organizations based on access-based consumption. It further evaluates a case study among small-scale producers in rural India, showing their acceptance for sharing vehicles. The newly created business opportunities will increase income and contribute to poverty alleviation. Taking part in the proposed truck sharing system can release them from ownership responsibilities, increase vehicle utilization as well as improve vehicle availability respectively speed of aid from the perspective of humanitarian organizations. This article highlights the applicability of business models relying on the idea of access-based consumption to not yet considered research fields. Especially the transfer to rural areas of developing countries makes this article uniqu
Keywords: Access-based; Consumption; Humanitarian; Logistics; Sustainable; Development; Developing; Countries

Offshore outsourcing of services: An evolutionary perspective - Tate, Wendy L.; Ellram, Lisa M.; Bals, Lydia; Hartmann, Evi (International Journal of Production Economics, 2009)
Offshore outsourcing is gaining increasing importance and attention in both theory and practice. The purpose of this research is to use nine in-depth case studies to analyze the evolution of offshore services outsourcing with regard to how expectations and governance structures change over time. Five testable propositions are presented, building on institutional theory, transaction cost, and resource-based perspectives. The cases demonstrate that offshore outsourcing is initiated because of increasing internal and external pressure to conform and reduce costs. Moreover, companies "chase" efficiency improvements in other geographic locations. But after reducing costs, companies discover more strategic benefits such as the potential to increase quality and market share. Importantly, as buyer-supplier relationships move from tactical to more strategic, expectations and governance structures change. © 2009 Elsevier B.V. All rights reserved.
WiSo-Import:2015-03-26:1017
Keywords: Transaction cost economics; Resource-based view; Offshoring; Offshore outsourcing; Institutional theory; Innovation

Offshore Outsourcing of Services: Decision Making Insights Beyond the Pursuit of Low Costs - Bals, Lydia; Hartmann, Evi; Tate, Wendy L.; Ellram, Lisa M. (19th North American Research/Teaching Symposium (NARS), 2008)
WiSo-Import:2015-04-17:1292
Keywords: Innovation

Offshoring - Analyse der Hintergründe und Potenziale - Jahns, Christopher; Hartmann, Evi; Bals, Lydia (Insourcing, Outsourcing, Offshouring, 2007)
Offshoring hat sich zu einem Schlagwort entwickelt, unter dem vielfältige Szenarien in Forschung und Praxis diskutiert werden. Es stellt sich die Frage, ob es sich wirklich um ein neues Phänomen oder um einen neuen Begriff für Outsourcing handelt. Wäre letzteres der Fall, so würde es sich nur um alten Wein in neuen Schläuchen handeln.
WiSo-Import:2015-04-20:1258
Keywords: Innovation

Offshoring: Determinants and Potentials of a New Business Concept - Jahns, Christopher; Hartmann, Evi; Bals, Lydia (Journal of Purchasing and Supply Management, 2006)
WiSo-Import:2015-03-26:1229
Keywords: Innovation

On the current state of combining human and artificial intelligence for strategic organizational decision making - Trunk, Anna; Birkel, Hendrik; Hartmann, Evi (Business Research, 2020)
Strategic organizational decision making in today’s complex world is a dynamic process characterized by uncertainty. Therefore, diverse groups of responsible employees deal with the large amount and variety of information, which must be acquired and interpreted correctly to deduce adequate alternatives. The technological potential of artificial intelligence (AI) is expected to offer further support, although research in this regard is still developing. However, as the technology is designed to have capabilities beyond those of traditional machines, the effects on the division of tasks and the definition of roles established in the current human–machine relationship are discussed with increasing awareness. Based on a systematic literature review, combined with content analysis, this article provides an overview of the possibilities that current research identifies for integrating AI into organizational decision making under uncertainty. The findings are summarized in a conceptual model that first explains how humans can use AI for decision making under uncertainty and then identifies the challenges, pre-conditions, and consequences that must be considered. While research on organizational structures, the choice of AI application, and the possibilities of knowledge management is extensive, a clear recommendation for ethical frameworks, despite being defined as a crucial foundation, is missing. In addition, AI, other than traditional machines, can amplify problems inherent in the decision-making process rather than help to reduce them. As a result, the human responsibility increases, while the capabilities needed to use the technology differ from other machines, thus making education necessary. These findings make the study valuable for both researchers and practitioners.<br

Operational focus: Sourcing in the Process Industries Fashionable Again? - Hartmann, Evi; Salehi, F.; Vallerien, S. (Chemical Market Reporter, 2003)
The importance of procurement during the recent recessive times is discussed. A tailor made sourcing strategy can significantly increase the profitability, market share and technological innovation of process companies. Companies are pursuing strategic sourcing applications in line with the sourcing categories and are readily adapting to e-procurement tools.
WiSo-Import:2015-03-26:1246
Keywords: Innovation

Opportunism Risk in Service Triads: A Social Capital Perspective - Herb, Stefan; Hartmann, Evi (International Journal of Physical Distribution & Logistics Management, 2014)
WiSo-Import:2015-03-26:4749

Organisational design implications of global sourcing: A multiple case study analysis on the application of control mechanisms - Hartmann, Evi; Trautmann, Gerhard; Jahns, Christopher (Journal of Purchasing and Supply Management, 2008)
Global sourcing has become an intended practice for many multinational corporations. Organisational design implications of global sourcing are rarely considered although they are one of the main facets of a global sourcing strategy. By elaborating on the information processing perspective of contingency theory, we derive explanations for the application of different control mechanisms in the global sourcing context. Our findings from case studies at eight multinational companies suggest that variations in control mechanisms can be explained by two contingencies: (1) corporate organisational structure and (2) the distribution of purchasing expertise among subsidiaries. Based on these case study findings, we formulate ten propositions for future research.
WiSo-Import:2015-03-26:1023
Keywords: Purchasing organisation; International management; Global sourcing; Control mechanisms; case studies; Innovation

Organizational Implications of Global Sourcing - Hartmann, Evi; Jahns, Christopher; Trautmann, Gerhard (16th International Purchasing & Supply Education & Research Association (IPSERA), 2007)
WiSo-Import:2015-04-17:1312
Keywords: Innovation

Organizational resilience driven by business model innovation: Insights from the food supply chain - Münch, Christopher; Hartmann, Evi (International Journal of Logistics Management, 2022)

Outsourcing Logistics Functions - Hartmann, Evi; Birkel, Hendrik; Kopyto, Matthias (2021)
Outsourcing describes the execution and management of activities or functions by external specialized service providers and includes both material goods and services. As today's complex value networks continue to extend globally, the process of logistics outsourcing remains an increasingly important issue. In particular, the transport of goods to link the nodes of networks and ensure seamless production activities is crucial. This article presents a holistic picture of the outsourcing of logistics functions to service providers and deals in particular with the development and structure of outsourcing and its individual process steps. The motivation for outsourcing is outlined by identifying advantages and enablers. In addition, this article shows which risks need to be considered both for the decision and for the management of outsourcing projects. Finally, external factors influencing the market environment are discussed.<br
Keywords: Contracting out; External service provider; Fourth-party logistics; 4PL; Logistics; Logistics management; Make or buy; Outsourcing; Supply chain management; Transportation; Third-party logistics; 3PL

Performance implications of low-cost country sourcing: an empirical investigation - Jahns, Christopher; Hartmann, Evi; Lockström, M. (1st International Conference on Operations and Supply Chain Management, 2005)
WiSo-Import:2015-04-17:1335
Keywords: Innovation

Performance Measurement and Antecedents of Early Internationalizing Firms: A Systematic Assessment - Rättich, Gordian; Clark, K.; Hartmann, Evi (Four Essays on International Entrepreneurship, 2011)
With the increasing importance of early internationalizing firms (EIFs), recent literature has shown a rapidly growing research interest in EIF performance. To enhance our understanding of what drives EIF performance, we conduct a systematic analysis of performance antecedents and performance measures in current empirical research. This method allows us to: (i) systematically analyze EIF literature to identify how performance has been examined empirically; (ii) methodically identify and synthesize the antecedents of performance in respect to EIFs’ specific resources, capabilities, and strategies; and (iii) to identify areas that are understudied. Based on the analysis, we make suggestions for future research.
Keywords: Performance Measurement; Antecedents of Early Internationalizing; Firms; A Systematic Assessment

Performance Measurement Systeme und Benchmarking als integrierter Ansatz zur Leistungsmessung der Flughafenlogistik - am Beispiel Ramp Services - Jahns, Christopher; Hartmann, Evi; Schmidberger, S. (Aviation Management, 2007)
WiSo-Import:2015-04-20:1259
Keywords: Innovation

Pollution Prevention and Service Stewardship Strategies in the Third-Party Logistics Industry: Effects on Firm Differentation and the Moderating Role of Environmental Communication - Maas, Steffen; Schuster, Tassilo; Hartmann, Evi (Business Strategy and the Environment, 2014)
A growing number of firms are considering the incorporation of environmental thinking into their business strategies, hoping to improve their competitiveness. In this paper, we analyze the effects of pollution prevention and service stewardship capabilities on firm differentiation advantage in the third-party logistics industry. Since prior research claims that complementary assets play an important role in fully understanding the environmental-management-competitiveness link, we furthermore examine the moderating role of environmental communication on the pollution-prevention-differentiation and the service-stewardship-differentiation linkages. We theoretically base our research in natural-resource-based thinking. Drawing on survey data, we apply multivariate regression and moderation analysis. The results highlight that pollution prevention and service stewardship capabilities can help third-party logistics providers to achieve a differentiation advantage. Also, the results show that environmental communication moderates the effect of pollution prevention on differentiation advantage and can hence be considered a valuable complementary asset.
Keywords: environmental thinking; business strategies; competitiveness; pollution prevention; service stewardship capabilities

Potentials of blockchain technology in supply chain management: Long-term judgments of an international expert panel - Kopyto, Matthias; Lechler, Sabrina; von der Gracht, Heiko A.; Hartmann, Evi (Technological Forecasting and Social Change, 2020)
Blockchain technology offers numerous fields of application, especially for supply chain management (SCM), as it could supersede the middleman activities in many transaction-based processes along the supply chain. Blockchain technology has a disruptive impact on supply chain design and operations, making the exploration of future application scenarios of great importance. However, knowledge in this field remains scarce, despite the subject's strategical value. This empirical study addresses this gap by conducting an interdisciplinary Delphi survey. Long-term judgments from an international panel of 108 designated experts from academia, industry, and politics/associations with different context-related backgrounds (blockchain, SCM, hybrid functions) were systematically analyzed. The results reveal prospective scenarios how blockchains will be applied in SCM by 2035 and which SCM-specific obstacles need to be solved in advance. One key finding reveals that even though blockchain technology is said to enable transactions between untrusted parties, trust-related advantages of blockchain technology are not directly transferable to SCM without additional conditions. Counterintuitively, active trust management between supply chain partners will still be needed. Nonetheless, this research reveals that blockchain technology will be strongly applied in SCM by 2035 and thus provides beneficial orientation and stimulating perspectives for decision-makers in the field.<br
Keywords: Blockchain; Future; Technology; Supply Chain; Expert judgments; Delphi study

Power & Reach: Die Macht der Einkäufer - Hartmann, Evi (Beschaffung aktuell, 2008)
Wie mächtig ist der Einkauf wirklich? Eine Studie des Supply Management Institute zusammen mit McKinsey zeigt sehr eindrücklich die Unterschiede zwischen im herkömmlichen Sinne „mächtigen“ Einkäufern und den relativ Machtlosen. Vor allem zeigt sie eines: Mächtige Einkäufer sind gut fürs Unternehmen.
WiSo-Import:2015-03-26:1234
Keywords: Innovation

Prevailing Technologies and Adoption Obstacles in Maritime Logistics - Wohlleber, Annika; Münch, Christopher; Hartmann, Evi (Proceedings of the Hamburg International Conference of Logistics (HICL), 2022)
Purpose: Digital technologies (DTs) are transforming logistics operations in the shipping industry. Yet, the industry is only in the early stages of digitalization. Consequently, there is a lack of empirical evidence on applied DTs and related obstacles for DT adoption. Methodology: A multiple case study was conducted comprising ports, freight forwarders, and carriers. Based on 18 expert interviews and additional data sources, differences and similarities concerning currently applied DTs and associated obstacles to DT adoption were examined. Findings: Presented findings indicate comprehensive efforts toward a paperless and digitalized way of operating within maritime container logistics (MCL) by using DTs such as blockchain, cloud solutions, and artificial intelligence. Especially ports strive to achieve collaborative data usage but are frequently hindered by a lack of inter-organizational data sharing. Furthermore, the inherent complexity of the MCL chain and employees’ and managers’ defensiveness toward technological change needs to be overcome by applying suitable measures for DT adoption. Originality: The research contributes to the scarce literature of DT adoption within MCL by providing empirical insights into the state-of-the-art of DTs for ports, freight forwarders, and carriers. Additionally, this research is the first to address implications for tackling existing obstacles for successful DT adoption in MCL<br
Keywords: Maritime logistics; Digital technologies

Produktion. Problemfelder der Produktion im Überblick - Hartmann, Evi; Kaiser, Gernot (Logistics and Supply Chain Management, 2005)
WiSo-Import:2015-04-20:1268
Keywords: Innovation

Purchasing Advertising Services – Analysis of the Purchasing Process and the Implications on Category Management - Bals, Lydia; Hartmann, Evi; Jahns, Christopher (22nd Industrial Marketing and Purchasing (IMP) conference, 2006)
WiSo-Import:2015-04-17:1318
Keywords: Innovation

Purchasing Competence: A Stakeholder-Based Framework for Chief Purchasing Officers - Kern, Daniel; Moser, Roger; Sundaresan, N.; Hartmann, Evi (Journal of Business Logistics, 2011)
A specific research stream within the purchasing and supply management literature focuses on the development of purchasing competence frameworks. We apply stakeholder theory and multiple methods of data collection to develop and confirm a hierarchy-specific purchasing competence management framework for Chief Purchasing Officers and validate it using confirmatory factor analysis on empirical data from 124 multinational companies. The results reveal a significant relationship between Chief Purchasing Officers purchasing management competence and different purchasing performance measures confirming the appropriateness of stakeholder theory for such a competence framework.
WiSo-Import:2015-03-26:1010
Keywords: stakeholder theory; purchasing performance; purchasing competence; Innovation; confirmatory factor analysis; Chief Purchasing Officers

Purchasing marketing services: Aligning purchasing and marketing to improve agency performance - Bals, Lydia; van der Valk, Wendy; Wynstra, F.; Hartmann, Evi (16th International Purchasing & Supply Education & Research Association (IPSERA), 2007)
WiSo-Import:2015-04-17:1306
Keywords: Innovation

Purchasing Marketing Services: Optimization Issues and Priorities - Bals, Lydia; Hartmann, Evi; Jahns, Christopher (Herbsttagung der Wissenschaftlichen Kommission Produktionswirtschaft des Verbands der Hochschullehrer für Betriebswirtschaft e.V., 2008)
WiSo-Import:2015-04-17:1291
Keywords: Innovation

Purchasing’s impact on postmerger performance: Effects of interaction with other business functions and suppliers - Hartmann, Evi; Romero Pérez, R. (24th Industrial Marketing and Purchasing (IMP) conference, 2008)
WiSo-Import:2015-04-17:1300
Keywords: Innovation

Quality is free – New Empirical Evidence from Manufacturing - Plewa, Markus; Kaiser, Gernot; Hartmann, Evi; Feisel, Edda (Academy of Management Journal, 2015)
We provide new empirical evidence for competing representations of the prevention-appraisal-failure model of quality cost. Using a large, unique data set for secondary analysis, combined with employing a high-level measure for overall quality performance, we validate the aggregate explanatory power of the prevalent cost of quality model variants. We conduct regression analysis to reveal relationships among total cost of quality, its components and overall quality performance. As a result, total cost of quality and its failure cost component are observed significantly lower at higher levels of quality, while the prevention and appraisal cost components are not observed to be significantly higher at higher levels of quality. Consequently we propose a modification to the modern representation of the prevention-appraisal-failure model to explain the data consistently. The important management implication is that in manufacturing, ever higher levels of quality are associated with significantly lower quality cos
Keywords: Manufacturing; Quality; Management; Secondary; Data; Analysis

Real-time data processing in supply chain management: revealing the uncertainty dilemma - Lechler, Sabrina; Canzaniello, Angelo; Roßmann, Bernhard; von der Gracht, Heiko A.; Hartmann, Evi (International Journal of Physical Distribution & Logistics Management, 2019)
Purpose: Particularly in volatile, uncertain, complex and ambiguous (VUCA) business conditions, staff in supply chain management (SCM) look to real-time (RT) data processing to reduce uncertainties. However, based on the premise that data processing can be perfectly mastered, such expectations do not reflect reality. The purpose of this paper is to investigate whether RT data processing reduces SCM uncertainties under real-world conditions. Design/methodology/approach: Aiming to facilitate communication on the research question, a Delphi expert survey was conducted to identify challenges of RT data processing in SCM operations and to assess whether it does influence the reduction of SCM uncertainty. In total, 14 prospective statements concerning RT data processing in SCM operations were developed and evaluated by 68 SCM and data-science experts. Findings: RT data processing was found to have an ambivalent influence on the reduction of SCM complexity and associated uncertainty. Analysis of the data collected from the study participants revealed a new type of uncertainty related to SCM data itself. Originality/value: This paper discusses the challenges of gathering relevant, timely and accurate data sets in VUCA environments and creates awareness of the relationship between data-related uncertainty and SCM uncertainty. Thus, it provides valuable insights for practitioners and the basis for further research on this subject.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Delphi survey; Real-time data processing; Supply chain management; Uncertainty; VUCA

Relationship Success Through The Appropriate Fit Between Purchase Situation and B2B E-Marketplace - Hartmann, Evi; Ritter, Thomas; Gemünden, Hans Georg (31st European Marketing Conference EMAC, 2002)
WiSo-Import:2015-04-17:1341
Keywords: Innovation

Rent-based Supplier Management Behavior - An Explorative Study - - Jahns, Christopher; Moser, Roger; Hartmann, Evi; Lockström, M. (18th North American Research/Teaching Symposium (NARS), 2007)
WiSo-Import:2015-04-17:1315
Keywords: Innovation

Research on the Phenomenon of Supply Chain Resilience: A Systematic Review and Paths for Further Investigation - Hohenstein, Nils Ole; Feisel, Edda; Hartmann, Evi; Giunipero, Larry (International Journal of Physical Distribution & Logistics Management, 2015)

Resilience through supply ecosystems - Challenges in transforming the supply chain into a supply ecosystem as a response to crises and disruptions - Münch, Christopher; Marx, Emanuel; Hartmann, Evi; Matzner, Martin (Proceedings of the Annual International Purchasing & Supply Education & Research Association (IPSERA) Conference, 2021)

Responding to the COVID-19 pandemic – catching up in the food industry through business model innovation - Münch, Christopher; Hartmann, Evi (International Journal of Logistics Management, 2023)
Purpose The food supply chain worldwide has suffered severely due to the COVID-19 pandemic countermeasures. Previous research suggests that business model innovation (BMI) could be a viable solution for recovering from the pandemic and fostering organizational resilience. This study analyzes the capabilities that enable food companies to innovate their business model and thereby increase organizational resilience. Design/methodology/approach Results were obtained using a multiple-case study approach consisting of 15 companies along the entire food supply chain. Managers and decision-makers were interviewed, and the collected insights were enriched with additional material. Findings The results show several capabilities that enable companies to innovate their business model due to disruption. These capabilities are categorized into four phases based on the processual representation of BMIs. Originality/value This study contributes to the understanding of BMI in the food supply chain and provides empirical evidence on the potential for business recovery through B

Reverse factoring in the supply chain: objectives, antecedents and implementation barriers - Liebl, John; Hartmann, Evi; Feisel, Edda (International Journal of Physical Distribution & Logistics Management, 2016)
Purpose Reverse factoring (RF) can generate win-win situations for buyers, banks and suppliers. However, the supply chain management literature generally tends to ignore financial influences and accounting support structures. Research in the area of RF is relatively new and considerably fragmented. The purpose of this paper is to address this research gap and provide an analysis of the objectives, antecedents and barriers of implementation. Design/methodology/approach The study contributes fundamental new insights derived from 11 case studies. In total, 28 interviews were conducted from the perspective of buyers, banks and suppliers and analyzed regarding influencing factors of different RF approaches. Findings RF predominantly is used to extend days payable outstanding. However, secondary objectives such as the reduction of supplier default risk and process simplifications also play an important role. The number of integrated suppliers, dependence of suppliers on their buyers, spread between internal refinancing and RF costs and the diversity of target agreements strongly influence these objectives and therefore the configuration of RF solutions. Originality/value Most studies fall short of exploring the mechanism of RF from all of the different perspectives of buyers, banks and suppliers. This approach allows new insights regarding prerequisites and different motivations behind RF.
Keywords: Case; study; Supply; chain; finance; Reverse; factoring; Financial; supply; chain; management

RFID in Retail Supply Chains: Current Developments and Future Potential - Rogers, Helen; Abd El Hakam, Talat; Hartmann, Evi; Gebhard, Marina (Springer Verlag, 2014)
This paper presents a study that investigates the implementation of RFID projects in German and Swiss retail supply chains from a qualitative perspective. The semi-structured interviews with experts from companies in the retail supply chain sector enabled us to gain insights into the problems RFID implementations have to face, as well as the benefits associated with them. In conjunction with a literature review, this allows us to identify the future challenges and potential of RFID applications in the retail industry.
Keywords: Logisitcs; Management; RFID; Retail; Developments; Future Potential

Risks of Industry 4.0 for Logistics - a Systematic Literature Review - Voigt, Kai-Ingo; Hartmann, Evi; Rücker, Marc; Veile, Johannes; Birkel, Hendrik (International Symposium on Logistics (ISL), 2019)

Robust capacitated facility location model for acquisitions under uncertainty - De Rosa, V.; Hartmann, Evi; Gebhard, Marina; Wollenweber, Jens (Computers & Industrial Engineering, 2014)

Robust sustainable bi-directional logistics network design under uncertainty - De Rosa, V.; Gebhard, Marina; Hartmann, Evi; Wollenweber, Jens (International Journal of Production Economics, 2013)

Sourcing in Emerging and Transition Economies: A Resource-Based View on Performance Implications - Jahns, Christopher; Hartmann, Evi; Lockström, M. (15th International Purchasing & Supply Education & Research Association (IPSERA)/17th North American Research/Teaching Symposium (NARS), 2006)
WiSo-Import:2015-04-17:1325
Keywords: Innovation

Stakeholder pressures, environmental practice adoption and economic performance in the German third-party logistics industry : a contingency perspective - Maas, Steffen; Schuster, Tassilo; Hartmann, Evi (Journal of Business Economics, 2018)
This study explores how companies adopt environmental practices when they are exposed to stakeholder pressures and how those practices affect economic performance within the German third-party logistics industry. The relationships are tested against a random sample of 192 German third-party logistics providers by using a higher-order partial least squares approach. The study reveals that perceived stakeholder pressures, especially internal, market, and regulatory pressures, strongly influence third-party logistics providers’ environmental practice adoption and that environmental practice adoption improves economic performance. Moreover, by introducing complexity of service offerings as an important firm-related contextual variable, the study advances our knowledge as it highlights that companies with basic service offerings can benefit more from adopting environmental practices than companies with advanced service offerings.<br

Strategic alignment and purchasing efficacy: an exploratory analysis of their impact on financial performance - Baier, Christian; Hartmann, Evi; Moser, Roger (Journal of Supply Chain Management, 2008)
Purchasing and supply management (PSM) has become a discipline of major strategic importance for effectively competing in today's global marketplace. Literature recognizes that the full value-creation potential of the purchasing function can only be realized if its decisions and activities are aligned with the organization's overall strategic orientation. Despite general agreement on this matter, research and practice lacks knowledge on how exactly such an alignment can be achieved and what performance implications it has. Therefore, this article empirically investigates the alignment–performance link in PSM in a comprehensive manner. Drawing on the theory of production competence, we suggest that the relative fit between business strategy and purchasing strategy, labeled as strategic alignment, and between purchasing strategy and purchasing practices, referred to as purchasing efficacy, is key to achieving superior financial performance. Results from profile deviation analysis on data collected globally from 141 strategic business units (SBUs) with revenues greater than USS3 billion support our hypotheses. Findings provide clear guidance to managers on how to design their purchasing strategies and practices to achieve maximum alignment and thus to effectively contribute to the SBU's financial success.
WiSo-Import:2015-03-26:1020
Keywords: Supply management; strategy development; regression analysis; profile deviation analysis; procurement/purchasing; fit/alignment; Innovation

Strategisches Supply Performance Measurement: Kostenbasierte Leistungsmessung in Einkauf und Supply Management - Jahns, Christopher; Hartmann, Evi; Entchelmeier, Aiko (Performance excellence - Zeitschrift für Controlling und Innovationsmanagement, 2007)
Die eigenen Wertschöpfungstiefen nehmen quer durch alle Branchen ab und betragen durchschnittlich nur noch ca. 40 – 50 %. Mit dieser Entwicklung einhergehend entwickelt sich der Einkauf zur strategischen Supply Management- Konzeption weiter. Das Supply Performance Measurement spielt zur Steuerung des Supply Managements eine wichtige Rolle. Auch von Seiten der Bedarfsträger, der Unternehmensführung und der Shareholder wird eine Messung des Erfolgs des Supply Managements mittlerweile nachhaltig gefordert. Im Mittelpunkt der Leistungsmessung des Supply Managements steht die monetäre Messung der Supply Performance. Hierzu lassen sich sechs verschiedene Verfahren zur Messung der Einsparungen des Supply Managements identifizieren. Will das Supply Management nachhaltige Erfolge erzielen und seinen Wertbeitrag ausweisen, muss es seine Einsparungen („Savings“) in einer durchgängigen Systematik (Savingsframework) transparent machen. Die Savingskonzepte sind dabei unter Berücksichtigung des Total Cost of Ownership-Ansatzes und durch den Aufbau eines Realisierungscontrollings zu einem umfassenden kostenbasierten Supply Performance Measurement weiterzuentwickeln. Am Beispiel des Savingsframeworks der Deutschen Post World Net wird ein Ansatz zur Messung und Steuerung der kostenbasierten Supply Performance in der Unternehmenspraxis vorgestellt
WiSo-Import:2015-03-26:1227
Keywords: Innovation

Strategisches Wertschöpfungsmanagement - Jahns, Christopher; Hartmann, Evi (Purchasing and Supply Management, 2005)
WiSo-Import:2015-04-20:1270
Keywords: Innovation

Supplier Evaluation at EADS - Jahns, Christopher; Moser, Roger; Hartmann, Evi (Process Management. Creating Value along the Supply Chain, 2008)
WiSo-Import:2015-04-20:1253
Keywords: Innovation

Supply chain governance in the context of industry 4.0: Investigating implications of real-life implementations from a multi-tier perspective - Pfaff, Yuko; Birkel, Hendrik; Hartmann, Evi (International Journal of Production Economics, 2023)
This paper addresses the impact of Industry 4.0 (I4.0) on supply chain governance (SCG) mechanisms within inter-organizational relationships in a multi-tier context. Special emphasis is paid to the investigation of the dynamics and outcome with regard to the structure and management of the relationships along the multi-tier. A multiple case study method is applied to explain the impact of I4.0 based on a theory-grounded research framework through the lens of complementary SCM theories. Building on qualitative in-depth interviews with 19 experts in managerial positions, three cases from the manufacturing industry involving an I4.0 implementation across the multi-tier were analyzed. This research demonstrates an intensification of synergistic combinations of inter-firm resources, emphasizing SCG as essential. With the implementation of I4.0, competitive advantage along the multi-tier takes higher priority over the competitive advantage in the individual or dyadic perspective. Relational governance mechanisms evolve, allowing competitive advantage as a multi-tier balancing out traditional power mechanisms within the supply chain hierarchy. Findings show that contractual governance mechanisms are limited in their effect, revealing the need for an evolution of “relational contracting.” Finally, the case research proposes “agility” as an extended mechanism in SCG research. The study offers in-depth insights into the structure of SCG mechanisms and the implications of adapted SCG on SCM outcomes to redesign multi-tier relationships. Supported by SCM theories and the dimensions of SCG, this paper contributes to the first insights beyond the dyadic perspective, providing an integrated multi-tier perspective while discussing specific mechanisms and identifying relevant propositions for future researc

Supply chain operations value – a new way of measuring cost-performance relations - Liebl, John; Hartmann, Evi; Feisel, Edda (DSI Annual Meeting 2016, 2016)

Supply Chain Risikomanagement - Hartmann, Evi; Birkel, Hendrik (Wirtschaftswissenschaftliches Studium, 2020)
Globale Versorgungsnetze sind durch eine hohe Komplexität mit einer Vielzahl von Risiken gekennzeichnet und müssen nicht nur wirtschaftlich sondern auch wettbewerbsfähig sein. Diese Unternehmensaufgabe wird als Supply Chain Risikomanagement bezeichnet und gewinnt in Wissenschaft und Praxis zunehmend an Bedeutung. Zur besseren Klassifizierung dieses Themengebiets befasst sich dieser Beitrag mit der Erläuterung zentraler Begrifflichkeiten, dem Risikoprozess sowie dem Einfluss neuer Technologien.<br

Supply Chain Services from a Service-dominant Perspective: A Content Analysis - Maas, Steffen; Herb, Stefan; Hartmann, Evi (International Journal of Physical Distribution & Logistics Management, 2014)
WiSo-Import:2015-03-26:4752

Supply Controlling: Ausbildung einer eigenständigen Führungsunterstützungsfunktion für Einkauf und Supply Management - Jahns, Christopher; Hartmann, Evi; Entchelmeier, Aiko (Herbsttagung der Wissenschaftlichen Kommission Produktionswirtschaft des Verbands der Hochschullehrer für Betriebswirtschaft e.V. 2006, 2006)
WiSo-Import:2015-04-17:1322
Keywords: Innovation

Supply Frühwarnsysteme (II): Implementierung eines Supply Frühwarnsystems bei der Robert Bosch GmbH - Moder, Marco; Meyer, Peter; Jahns, Christopher; Hartmann, Evi (Beschaffung aktuell, 2007)
Mit steigender Abhängigkeit von den eigenen Lieferanten und einer immer komplexeren Umweltsituation steigt auch in der Unternehmenspraxis die Notwendigkeit, Supply Risk Management-Konzepte zu implementieren. Im Folgenden wird am Beispiel des Geschäftsbereichs Automobilelektronik der Robert Bosch GmbH ein besonders umfassender Ansatz vorgestellt, wie ein Supply Frühwarnsystem in der Praxis implementiert werden kann.
WiSo-Import:2015-03-26:1241
Keywords: Innovation

Supply Frühwarnsysteme (I): Kritische Risiken im Supply Management frühzeitig erkennen - Jahns, Christopher; Hartmann, Evi; Moder, Marco (Beschaffung aktuell, 2006)
WiSo-Import:2015-03-26:1242
Keywords: Innovation

Supply Frühwarnsysteme in der Automobilindustrie - Moder, Marco; Hartmann, Evi; Moser, Roger (Business Focus China: Automobilindustrie, 2009)
WiSo-Import:2015-04-20:1249
Keywords: Innovation

Supply Key Account Management - Jahns, Christopher; Hartmann, Evi; Reinhardt, Sando (Beschaffung aktuell, 2006)
Der Einkauf muss sich vom Selbstverständnis eines untergeordneten Dienstleisters lösen und zum strategischen Partner seiner internen Kunden aufsteigen, wenn er seiner großen Bedeutung für die Wettbewerbsfähigkeit des Unternehmens Rechnung tragen will. Ein Blick in die Marketing- und Vertriebsabteilungen zeigt, dass dort schon lange an ähnlichen Fragestellungen gearbeitet wird. Deren Erkenntnisse können auf das Supply Management übertragen werden.
WiSo-Import:2015-03-26:1243
Keywords: Innovation

Supply Network Configuration Benchmarking: Framework Development and Application in the Indian Automotive Industry - Moser, Roger; Kern, Daniel; Wohlfarth, S.; Hartmann, Evi (Benchmarking, 2011)
Purpose: The purpose of this paper is to develop a benchmarking framework for the analysis of the supply network configuration of companies and exemplify its applications in the Indian automotive sector. Design/methodology/approach: The authors combine elements of relationship and network theories from different research streams to develop a three-level supply network configuration benchmarking framework including a dyadic supply chain and network perspective. The analysis of two case companies exemplifies how different supply networks in emerging markets are depending on the specific strategies and institutional context. Findings: The framework works well with the two case studies presented. A major player in the Indian automotive industry is benchmarked against a newcomer in this emerging country. The results can be used to improve each firm's supplier base management approach and create more efficiency in their further development. Originality/value: This paper builds on current theories to develop a benchmarking framework for supply network configuration analysis combining the dyadic, chain, and network level into one framework. The case example exemplifies the developed framework. © Emerald Group Publishing Limited.
WiSo-Import:2015-03-26:1011
Keywords: Innovation

Supply Performance Mearsurement: Towards an Integrated Framework - Jahns, Christopher; Hartmann, Evi; Entchelmeier, Aiko (15th International Purchasing & Supply Education & Research Association (IPSERA)/17th North American Research/Teaching Symposium (NARS), 2006)
WiSo-Import:2015-04-17:1323
Keywords: Innovation

Supply Performance Measurement Systems:Viewed from an Information Processing Perspective - Reuter, C.; Hartmann, Evi; Jahns, Christopher (17th International Purchasing & Supply Education & Research Association (IPSERA), 2008)
WiSo-Import:2015-04-17:1299
Keywords: Innovation

Supply Risk Assessment: A Utility Value Based Concept - Entchelmeier, Aiko; Hartmann, Evi; Henke, Michael (22nd Industrial Marketing and Purchasing (IMP) conference, 2006)
WiSo-Import:2015-04-17:1319
Keywords: Innovation

Supply Risk Management: Model Development and Empirical Analysis - Kern, Daniel; Moser, Roger; Hartmann, Evi; Moder, M. (International Journal of Physical Distribution & Logistics Management, 2012)
Purpose: The purpose of this paper is to develop a model for upstream supply chain risk management linking risk identification, risk assessment and risk mitigation to risk performance and validate the model empirically. The effect of a continuous improvement process on identification, assessment, and mitigation is also included in the model. Design/methodology/approach: A literature review is undertaken to derive the hypotheses and operationalize the included constructs. The paper then tests the path analytical model using partial least squares analyses on survey data from 162 large and mid-sized manufacturing companies located in Germany. Findings: All items load high on their respective constructs and the data provides robust support to all hypothesized relationships. Superior risk identification supports the subsequent risk assessment and this in turn leads to better risk mitigation. The model explains 46 percent of the variance observed in risk performance. Research limitations/implications: This study empirically validates the sequential effect of the three risk management steps on risk performance as well as the influence of continuous improvement activities. Limitations of this study can be seen in the use of perceptional data from single informants and the focus on manufacturing firms in a single country. Practical implications: The detailed operationalization of the constructs sheds further light on the problem of measuring risk management efforts. Clear evidence of the performance effect of risk management provides managers with a business case to invest in such initiatives. Originality/value: This is one of the first large-scale, empirical studies on the process dimensions of upstream supply chain risk management. © Emerald Group Publishing Limited.
WiSo-Import:2015-03-26:3119
Keywords: Continuous improvement; Germany; Manufacturing industries; Partial least squares; Structural equations model; Supply chain risk management; Survey data

Supply Strategies and the Supply Strategy Portfolio - Case Study - Hartmann, Evi; Bals, Lydia; Trautmann, Gerhard (Proceedings of the 12th International Federation of Purchasing & Supply Management (IFPSM) Summer School 2006, 2007)
WiSo-Import:2015-04-17:1309
Keywords: Innovation

Supply Techniques - Hartmann, Evi; Moser, Roger (Purchasing and Supply Management, 2005)
WiSo-Import:2015-04-20:1269
Keywords: Innovation

Sustainability management beyond organizational boundaries-sustainable supplier relationship management in the chemical industry - Leppelt, T.; Foerstl, K.; Reuter, C.; Hartmann, Evi (Journal of Cleaner Production, 2011)
WiSo-Import:2015-03-26:3117

Sustainable development through cross-company collaboration: an automotive case study of alliance phenomenon - Benz, Lukas; Münch, Christopher; Hartmann, Evi (Production and Operations Management Society (POMS), 2021)
In global supply chains, particularly at the bottom of the pyramid in emerging countries, sustainable development is a daunting challenge. Therefore, cross-company alliances are formed to enhance sustainability. Aim of this research is to analyze alliances based on an ellaborated framework by conducting a case study within the automotive industry.<br

Sustainable Global Supplier Management – The Role of Dynamic Capabilities in Achieving Competitive Advantage - Reuter, Carsten; Förstl, Kai; Hartmann, Evi; Blome, Constantin (Journal of Supply Chain Management, 2010)
Organizations face increased pressure from stakeholders to incorporate a plethora of corporate responsibility (CR) and sustainability aspects in their business practices. Legal and extra-legal demands are dynamically changing; almost no organizational function is unaffected. Owing to the outsourcing wave of the last decade, in particular purchasing and supply management (PSM) plays an ever more important role in assuring sustainable production of the firm's products offered in the marketplace. The supply base of many Western firms has become increasingly global and spend volumes have shifted towards emerging countries. In order to avoid the risk of reputational damage to the buying company, the PSM department must ensure that their international suppliers comply with their corporate codes of conduct and that environmental and social misconduct at supplier premises does not occur. In this paper, “sustainability” refers to the pursuit of the tripartite of economic, environmental, and social performance. We contribute to prior research in the fields of sustainability and CR by extending insights of the dynamic capabilities view to analyze how the PSM function integrates sustainability aspects in its global supplier management processes. Based on four case studies in the chemical industry, we propose that profound sustainable global supplier management (SGSM) capabilities are a source of competitive advantage. These capabilities are path dependent and particularly valuable when organizations are receptive to external stakeholder pressure. Early movers in the field of SGSM reap competitive benefits to a notable extent as a result of resource accumulation and learning processes over time.
Keywords: Sustainable Global Supplier Management; Dynamic Capabilities; Competitive Advantage

Systematic Analysis of Early Internationalizing Firm Performance - Rättich, Gordian; Clark, K.; Hartmann, Evi (Academy of International Business Annual Meeting, 2011)
WiSo-Import:2015-04-17:3121

Tabula rasa oder ein Platz zum Lernen? - Feisel, Edda; Hartmann, Evi; Schober, Holger; Schneppensiefer, Michael (Beschaffung aktuell, 2008)
China hat sich in den letzten Jahren mit niedrigen Lohn- und Materialkosten als klassischer Beschaffungsmarkt westlicher Unternehmen etabliert. Die Chancen liegen vor allem in den enormen Einsparpotenzialen und verbesserten Margen. Doch wo Chancen winken, lauern auch Risiken. Risiken, die alle Einspareffekte zunichte machen können und die Lieferfähigkeit von Produzenten bedrohen. Welche Risiken sind beim Sourcing in China besonders virulent? Und wie können sich Einkäufer und Supply Manager davor schützen?
WiSo-Import:2015-03-26:1233
Keywords: Innovation

Talent Management im Einkauf (I) - Feisel, Edda; Hartmann, Evi (Beschaffung aktuell, 2007)
WiSo-Import:2015-03-26:1235
Keywords: Innovation

Talent management of Western MNCs in China: Balancing global integration and local responsiveness - Hartmann, Evi; Feisel, Edda; Schober, Holger (Journal of World Business, 2012)
<span style="color: rgb(46, 46, 46); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: 16px; word-spacing: -1.24453px;">Since the beginning of its market economy and open-door policy in 1978, China has extensively promoted foreign direct investment. Consequently, many western MNCs have entered the country in search of new business opportunities. Today, one of the greatest challenges facing these organizations is finding talented people who are needed to run their businesses. Although the strategic importance of talent management has been acknowledged in recent years, few studies analyze the talent management of western MNCs in China. Building on qualitative data from seven case studies, our paper therefore seeks to explore how western MNCs in China identify, develop and retain their talented employees. The paper shows that MNCs transfer their talent management practices to China without many changes, focusing specifically on the development of talented employees and the creation of an organizational culture. Nevertheless, the results also indicate that integrated and strategic talent management strategies have not yet been fully implemented.
Keywords: Talent Management; China; Talent pools

Technology Assessment Using Satellite Big Data Analytics for India's Agri-Insurance Sector - Nagendra, Narayan Prasad; Narayanamurthy, Gopalakrishnan; Moser, Roger; Hartmann, Evi; Sengupta, Tuhin (IEEE Transactions on Engineering Management, 2022)
Over half of India's employment is attached to the agriculture sector and their survival is dependent on the performance of farms. The uncertainty in the performance of farms due to weather fluctuations and other risks is tackled by providing insurance cover. However, policymakers' choice of administrative measures for estimating crop loss has resulted in inaccurate data collection, opened vulnerability to the politicization of the process, and created bottlenecks to operate at scale. These problems have led to skewed timelines for data collation, lack of confidence in the data produced by the agri-insurance providers, and caused long-drawn delays in settling claims made by farmers. In this article, we present a case study on the assessment of using satellite big data as a technology deployed in Northern India to solve the aforementioned problems between the stakeholders in the agri-insurance claim settlement process. Satellite big data based analytics provides an independent data source and decision-making platform for the agri-insurers to conduct an assessment for calculating the indemnity payments. The results showcase how transparency brought in by the satellite big data analytics curbs the plausible exploitation of the claim settlement process and leads to increased efficiency and efficacy in settling farmer claims.
Created from Fastlane, WoS look-up

Technology foresight for sustainable road freight transportation: Insights from a global real-time Delphi study - Meyer, Tobias; von der Gracht, Heiko A.; Hartmann, Evi (Futures & Foresight Science, 2022)
Organizations increasingly adopt technologies and logistics measures to improve their social sustainability, reduce transportation-related carbon emissions, or even design their supply chains carbon negative. However, the speed at which this adoption is progressing is not fast enough to address the sustainability challenges of the world today. To gain deeper knowledge about the adoption process of sustainability-related measures in road freight transportation, this paper examines barriers currently hindering a broader market penetration and derives expected timeframes when mass adoption of 14 relevant technologies will occur. Furthermore, the technologies' impacts on the economic, environmental, and social dimensions of sustainability are discussed providing recommendations, on which technologies the respective stakeholders might focus on in the future. Since we want to examines a long-term technology perspective of the next 25 years, we rely on systematic foresight methodology. More specifically, we collect empirical data by use of a real-time Delphi survey, which particularly suits complex and uncertain environments. Our global panel includes 116 experts from 25 different countries. The assessments are grouped into short-term, midterm, midterm to long-term, and long-term developments. The categories shed light on potential drivers and barriers to the implementation of the surveyed technologies. The findings emphasize the need to systematically select suitable measures and promote those that are expected to deliver short-term sustainability improvements to address current deficits in a timely manner. The article further outlines the crucial role of politics in developing necessary regulative frameworks to drive sustainability in road freight transportation.
CRIS-Team Scopus Importer:2024-12-16
Keywords: battery electric trucks; carbon emissions; real-time Delphi survey; road freight transportation; sustainability; technology foresight

The bumpy road to the adoption of the Physical Internet – Overcoming barriers from a stakeholder perspective - Meyer, Tobias; Hartmann, Evi (6th International Physical Internet Conference Proceedings, 2019)
The Physical Internet aims for a paradigm shift by eliminating the unsustainability issues in today’s supply chain processes. The development of the concept in recent years has shown that the PI is still in its conceptualization phase. In order to increase the attention and adoption of the concept both, in literature and practice, empirical knowledge is needed concerning how and why affected stakeholders will adopt the concept. To address this gap, we gathered qualitative data through a single embedded case study approach. In total, we have integrated 14 stakeholders with verifiable expertise in the PI. The sample consists of logistics and transport service providers, shippers and includes companies selling or working on specific PI-products. Furthermore, we gathered empirical data from research institutes with specific knowledge or projects in the PI. This paper provides insights about the adoption of the PI and in particular about stakeholder intentions, organizational and technological readiness as well as barriers and drivers
Keywords: Physical Internet; Case Study; Open networks; Drivers

The Evolution of Offshore Outsourcing of Services: A Theoretical Perspective - Tate, Wendy L.; Ellram, Lisa M.; Hartmann, Evi; Bals, Lydia (38th Decision Sciences Institute Annual Meeting, 2007)
WiSo-Import:2015-04-17:1317
Keywords: Innovation

The Fit between Purchase Situation and B2B E-Marketplaces and Its Impact on Relationship Success - Hartmann, Evi; Ritter, Thomas; Gemünden, Hans Georg (18th Industrial Marketing and Purchasing (IMP) conference, 2002)
WiSo-Import:2015-04-17:1342
Keywords: Innovation

The Fit Between Purchase Situations and B2B E-Marketplaces and its Impact on Relationship Success - Hartmann, Evi; Ritter, Thomas; Gemünden, Hans Georg (Journal of Consumer Behaviour, 2002)
The internet is not a mere alternative channel for marketing or selling products online, instead electronic marketplace enables buyers and sellers to innovate whole business processes from sourcing and production to customer service. These changes will significantly impact business-to-business interactions and relationships as it offers new ways of collaborating across organizational boundaries. In this study the authors conceptualize the appropriate fit between purchase situation and B2B E-marketplace for optimizing the value creation as a set of direct and indirect functions of buyer-supplier relationships. The findings from an empirical study of 119 firms show that the appropriate fit especially contributes to the direct values of the supplier relationship. The results of this study have considerable consequences for relationship management.
WiSo-Import:2015-03-26:1231
Keywords: Sourcing; Relationship Management; Procurement; E-Procurement; E-Marketplace; e-commerce; B2B Marketing; Innovation

The Flexibility of Logistics Service Providers and its Impact on Customer Loyalty An Empirical Study - Hartmann, Evi; Grahl, Alexander (Journal of Supply Chain Management, 2011)
The use of logistics outsourcing and the degree of competition in the logistics service industry have significantly increased over the past decade. In order to reach and maintain an important role in such a business environment, logistics service providers (LSPs) have to find ways to achieve competitive advantage. In this regard, the role of flexibility as a potential source of competitive advantage for an LSP is unclear, as empirical research on flexibility in an industrial services context and specifically in logistics outsourcing relationships is lacking. Therefore, using the resource-based view theory as the theoretical foundation, this study develops a conceptual model of flexibility as a capability of an LSP and its impact on customer loyalty, a central outcome for LSPs in a competitive business environment. Further, taking a relational as well as a knowledge perspective with respect to the antecedents of flexibility, the relational capability collaboration and the knowledge resources supply chain partner insight and communication are integrated into the model. Finally, the relationships of collaboration as a capability with knowledge resources as well as with customer loyalty are considered. This study analyzes 155 logistics outsourcing relationships using a survey method and partial least squares structural equation modeling to empirically assess the proposed relationships. The results reveal that LSP flexibility is a strong driver of all core dimensions of customer loyalty (i.e., retention, extension and referrals) and thus a source of competitive advantage for LSPs. Further, collaboration positively influences LSP flexibility and also the loyalty dimensions, supporting its significant role in a supply chain relationship. Finally, knowledge resources have a positive effect on LSP flexibility as well as on collaboration, indicating the importance of such resources in facilitating crucial capabilities. © 2011 Institute for Supply Management, Inc.™</sup
WiSo-Import:2015-03-26:3118
Keywords: And logistics; Business-to-business marketing; Distribution; Logistics service providers; Outsourcing (make or buy); Structural equation modeling; Survey methods; Transportation

The future and social impact of Big Data Analytics in Supply Chain Management: Results from a Delphi study - Roßmann, Bernhard; Canzaniello, Angelo; von der Gracht, Heiko; Hartmann, Evi (Technological Forecasting and Social Change, 2018)
The continuously growing amount of available data has accelerated the emergence of numerous business intelligence applications that are summarized under the term Big Data Analytics (BDA). BDA is especially relevant to the domain of Supply Chain Management (SCM) as it provides the tools to support decision-making in increasingly global, volatile and dynamic value networks. However, its application challenges traditional institutional arrangements as well as roles that are related to the management of data. The underlying empirical study addresses this challenge with the application of a multi-method approach that is embedded in Organizational Information Processing Theory (OIPT). A Delphi survey was conducted to integrate expert assessments of projections up to the year 2035 and fuzzy c-means clustering was applied to identify future scenarios that span the future of BDA in SCM. The study suggests that BDA will improve demand forecasts, reduce safety stocks and improve the management of supplier performance. However, supply chain (SC) processes will become increasingly automated and traditional tasks of SCM will be partially substituted as a result. Consequently, the transition of the traditional role of SCM within organizations will increase the importance of human intuition, trust and strategic decision-makin
Keywords: Big Data Analytics; Supply Chain Management; Organizational Information Processing Theory; Delphi method; Fuzzy logic

The Future of Big Data Analytics in Supply Chain Management: Results from a Delphi Study - Roßmann, Bernhard; Canzaniello, Angelo; von der Gracht, Heiko; Hartmann, Evi (Academy of Management Proceedings, 2017)
The evermore growing amount of available data accelerated the emergence of numerous business intelligence applications that are summarised under the term Big Data Analytics (BDA). As value networks are becoming more global and complex while the amount of data is simultaneously increasing, BDA is especially relevant to the domain of supply chain management (SCM). Its application does challenge traditional institutional arrangements as well as roles that are related to the management of data. Our empirical study addresses this challenge by an application of a Delphi survey that is embedded in organisational information processing theory. For this purpose, we integrate the assessments of experts on projections up to the year 2035 to span the future of BDA in SCM. Our study suggests that BDA will improve demand forecasts, reduce safety stocks and improve the management of supplier performance. However, supply chain processes will become increasingly automated and traditional tasks of SCM are partially substituted in consequence. Consequently, the transition of the traditional role of SCM within organisations will increase the importance of human intuition, trust and strategic decision-makin

The future of industry 4.0 and supply chain resilience after the COVID-19 pandemic: Empirical evidence from a Delphi study - Spieske, Alexander; Gebhardt, Maximilian; Kopyto, Matthias; Birkel, Hendrik; Hartmann, Evi (Computers & Industrial Engineering, 2023)
The COVID-19 pandemic has caused major supply chain disruptions and unveiled the pressing need to improve supply chain resilience (SCRES). Industry 4.0 (I4.0) is a promising lever; however, its future in supply chain risk management (SCRM) is highly uncertain and largely unexplored. This paper aims to evaluate I4.0′s potential to improve SCRES in a post-COVID-19 world. Based on current literature and multiple workshops, 13 future projections on potential I4.0 application areas in SCRM were developed. A two-round Delphi study among 64 SCRM experts with digital expertise was conducted to evaluate and discuss the projections regarding their probability of occurrence until 2030, their impact on SCRES, and their desirability. A fuzzy c-means algorithm was applied to cluster the projections based on the expert assessments. The expert evaluations led to three clusters on I4.0 application in SCRM: Four projections on generating data, increasing visibility, and building digital capabilities received considerable approval and are reliable to improve SCRES in 2030. Four projections enabling data sharing and processing were predominantly supported and demonstrated realization potential for 2030. Finally, five projections that require major supply network adaptations were deemed unlikely to improve SCRES in 2030. This paper answers several research calls by presenting empirical evidence on the pathway of I4.0 implementation in SCRM following the COVID-19 pandemic. Moreover, it evaluates a holistic set of technologies and indicates prioritization potentials to achieve SCRES improvements.
CRIS-Team Scopus Importer:2023-06-09
Keywords: COVID-19 pandemic; Delphi study; Digital supply chain; Industry 4.0; Supply chain Resilience; Supply Chain Risk

The Future of Logistics in Emerging Markets – Fuzzy Clustering Scenarios Grounded in Institutional and Factor-Market Rivalry Theory - Hirschinger, Micha; Spickermann, Alexander; Hartmann, Evi; von der Gracht, Heiko; Darkow, Inga-Lena (Journal of Supply Chain Management, 2015)
Transportation and logistics are increasingly relevant to the rapid economic growth of emerging economies. Decision makers in the transportation and logistics industry require a comprehensive understanding of the institutional business environment and factor markets in emerging economy countries to formulate accurate supply chain strategies for the future. Although extensive studies on prospective scenarios in emerging economies are available, research has largely neglected the future evolution of transportation and logistics. This study addresses this gap by applying a multiple method research approach and relying on institutional theory and factor-market rivalry theory to create scenarios of the development of transportation and logistics in emerging economy countries by 2030. We do so by collecting qualitative and quantitative data through a Delphi survey and applying fuzzy clustering to group the results into meaningful and interpretable scenarios. Our results suggest that emerging economies will take advantage of free trade zones to consolidate their position in the international market and encourage investment. Consequently, logistics will experience rapid growth and value-added services will expand, propelling new players from developing economies onto the international stage. Our findings also suggest that the logistics service industry in emerging economy countries will undergo a significant consolidation process, leading to the possibility of factor-market rivalry among shippers. This suggests that shippers' social networks and personal contacts will increase in importance in the futur
Keywords: Transportation; Distribution; Logistics; Emerging; Economies; Institutional; Theory; Factor-market; Rivalry; Theory; Panel; Study; Fuzzy; Logic; Cluster; Analysis

The future role of reverse logistics as a tool for sustainability in food supply chains: a Delphi-based scenario study - Münch, Christopher; von der Gracht, Heiko A.; Hartmann, Evi (Supply Chain Management-An International Journal, 2021)
Purpose: The importance of integrating sustainability into business activities rises continuously. In addition to an established focus on forward logistics, there is a growing awareness of reverse logistics. Reverse logistics ensures sustainable practices and increases competitiveness for companies, but it also comes with challenges. Therefore, the implementation of reverse logistics is associated with uncertainties. This paper aims to fill this gap by analyzing the development and comprehensive potential of reverse logistics as a sustainability tool. Design/methodology/approach: To bridge the research gap, a real-time Delphi study was conducted. Through an extensive desk research, semi-structured interviews, and an expert workshop, 14 projections for the German food sector of 2040 were created. A total of 49 experts in the field of logistics, reverse logistics, and food logistics assessed the future projections concerning estimated probability, impact, and desirability of occurrence. Findings: The findings derived lead to three possible future scenarios as well as potential drivers and barriers that food companies, the government, and society need to consider to enable a successful transition towards implementing reverse logistics in food supply chains. Originality/value: The study examined the future role of reverse logistics as a sustainability tool in food supply chains. The results serve as a framework for decision-making on the sustainable orientation of business practices, leading to increased competitiveness and resilient business strategy. Several implications are derived for practitioners, policymakers, and society to promote reverse logistics. Methodologically, this study extends existing Delphi methods by conducting a quantitative dissent and sentiment analysis, considering various surface-level and deep-level diversity characteristics. <
Keywords: Closed-loop supply chains; Circular economy; Delphi method; Food industry; Food supply chain; Reverse logistics; Sustainability; Sustainable supply chain management

The impact of digitalization on the future of the PSM function managing purchasing and innovation in new product development – Evidence from a Delphi study - Wehrle, Manuel; Birkel, Hendrik; von der Gracht, Heiko A.; Hartmann, Evi (Journal of Purchasing and Supply Management, 2022)
Bringing innovative products to markets is essential for companies, especially in competitive environments. One of the driving forces for successful new product development (NPD) is the inclusion of the functions that form part of the process such as purchasing and supply management (PSM). While extensive research has been conducted on the role of procurement in promoting innovation, insufficient research on the future of the PSM function in NPD has been conducted. This study addresses this gap, considering increasing digitalization and its effect on the future PSM function managing purchasing and innovation. To explore the future of PSM in NPD, a Delphi survey with 91 experts from industry, academia, and politics or associations was performed. The results reveal that digitalization will influence the PSM function in NPD across different time horizons and forms depending on the subject area. While in many areas, an interplay between digital technologies and human PSM professionals is expected, in certain domains the PSM function is likely to lose added value compared to digital technologies. Furthermore, digitalization is expected to be a potential enabler of a stronger key innovation role for PSM in NPD but to also introduce new requirements such as data science capabilities.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Cross-impact analysis; Delphi study; Digitalization; Foresight; Judgmental forecasting; New product development; Purchasing and supply management

The impact of Human Resource Management (HRM) practices on purchasing skills and knowledge: A German Case Study - Feisel, Edda; Hartmann, Evi; Jahns, Christopher (19th North American Research/Teaching Symposium (NARS), 2008)
WiSo-Import:2015-04-17:1294
Keywords: Innovation

The Impact of Internal Purchasing Resources and Capabilities on Low-Cost Country Sourcing - Hartmann, Evi; Bals, Lydia; Kaiser, Gernot (Zeitschrift für Betriebswirtschaft (Spezial Issue), 2008)
There has been a steady rise of global sourcing practices within firms. A resource-based view model is used to empirically investigate how internal availability of resources and capabilities of the firm affects sourcing in low-cost countries. After a short introduction to the context and relevance of the research topic, the theoretical background of the resource-based view is detailed. Based on this, further literature as well as expert interviews, the constructs, hypotheses and the overall research model are presented. The empirical analysis is based on a survey. The survey data were gathered through structured telephone interviews with Chief Procurement Officers and Purchasing Managers of 156 large-sized companies in five European countries, part of a larger Low Cost Country Sourcing research project. They were analyzed with PLS (Partial Least Squares). The results show that as hypothesized, the availability of internal sourcing resources and capabilities has a high influence on what is sourced externally, with a positive impact on quality, time, costs and market performance.
WiSo-Import:2015-03-26:1022
Keywords: Innovation

The Impact of Internal Purchasing Resources and Capabilities on Sourcing in Emerging Countries: A Resource-based View - Hartmann, Evi; Bals, Lydia; Kaiser, Gernot (70. Wissenschaftliche Jahrestagung des Verbandes der Hochschullehrer für Betriebswirtschaft e.V. (VHB), 2008)
WiSo-Import:2015-04-17:1297
Keywords: Innovation

The importance of the human aspect in the supply function: Strategies for developing PSM proficiency - Feisel, Edda; Hartmann, Evi; Giunipero, Larry (Journal of Purchasing and Supply Management, 2011)
The rising percentage of purchasing volume and growing dependence on external suppliers has significantly broadened the responsibilities of the purchasing and supply management (PSM) function in recent years. Contrary to their administrative tasks in the past, PSM professionals now need to establish and foster long-term and strategic relationships with suppliers, while simultaneously reducing costs, managing supply risks and leveraging innovation capabilities. In order to contribute to the overall performance of a firm, research has emphasized that strong professional effectiveness is a vital prerequisite for achieving success in the function. Nevertheless, previous studies have not analysed how relevant skills can be developed. Building on qualitative data from four case studies, this article therefore extends previous work and explores the underlying strategies of skills development in the PSM function. By adapting a theoretical framework from human resource development (HRD) to the supply context, we analyse how various instruments influence the advancement of relevant skills and demonstrate how purchasing proficiency can be improved on four different performance levels. The article shows that PSM organisations have to carefully assess the strengths and weaknesses within their organisations before implementing any HRD activity and provides a useful means to better understand the development of the important human aspect in the functio
WiSo-Import:2015-03-26:1007
Keywords: Skills development; PSM professional; Innovation; Human resource development

The influence of specific behaviors towards strategic supply network partners on purchasing & supply management performance - Moser, Roger; Hartmann, Evi; Jahns, Christopher (22nd Industrial Marketing and Purchasing (IMP) conference, 2006)
WiSo-Import:2015-04-17:1331
Keywords: Innovation

The Influence of Specific Behaviours Towards Strategic Suppliers on Purchasing and Supply Management and Company Performance: An Empirical Study based on Partial Least Square (PLS) Analysis - Jahns, Christopher; Hartmann, Evi; Moser, Roger (11th International Symposium on Logistics (ISL), 2006)
WiSo-Import:2015-04-17:1329
Keywords: Innovation

The Influence of Strategy-driven Selection Priorities for Strategic Suppliers on Purchasing and Supply management and Company, Performance - Jahns, Christopher; Hartmann, Evi; Moser, Roger (15th International Purchasing & Supply Education & Research Association (IPSERA)/17th North American Research/Teaching Symposium (NARS), 2006)
WiSo-Import:2015-04-17:1321
Keywords: Innovation

The interplay between relationships, technologies and organizational structures in enhancing supply chain resilience: empirical evidence from a Delphi study - Küffner, Christoph; Kopyto, Matthias; Wohlleber, Annika; Hartmann, Evi (International Journal of Physical Distribution & Logistics Management, 2022)
Purpose COVID-19 has highlighted the need to reflect on how firms should improve their supply chains (SCs) to enhance agility and robustness. Recent studies focus more on the short-term rather than on the long-term developments and lack insights regarding the enhancement of supply chain resilience (SCRES) based on the interplay between multiple levers. Therefore, using a long-term perspective, this research evaluates the interaction between three SCRES levers – relationships, technologies and organizational structures – to improve SCRES. Design/methodology/approach Based on an extensive literature review, multiple interviews and workshops, 13 future projections were developed. These projections were assessed using a two-round Delphi study that included 83 international experts from industry, academia and politics/associations to determine the probability of occurrence by 2035, their impact on SCRES and their desirability. Findings This study provides empirical evidence that the long-term enhancement of SCRES is achieved through the interplay of multiple levers rather than unilateral optimization. The study suggests that, by 2035, collaboration between SC partners will be a key factor for SCRES enhancement. Additionally, SC stakeholders should be aware that failing to invest in digital technologies will negatively impact the agility and robustness of future SCs. Furthermore, humans are expected to continue to play a major role, given that relationship-oriented tasks are perceived to remain important. Originality/value This paper adds to current literature, describing how SCRES can be improved in the long term through the interplay of multiple levers and the combination of robust and agile elements. Considering the importance of ensuring resilient SCs, this paper provides valuable insights for academics and practitioner
Keywords: Supply chain resilience; Interplay; Relationships; Technologies; Organizational structures; Delphi study

The Link between Internal Purchasing and Supply Management (PSM) Practices, PSM Performance and Company Performance – Evidence from a Structural Equation Model - Hartmann, Evi; Foerstl, K.; Moser, Roger (24th Industrial Marketing and Purchasing (IMP) conference, 2008)
WiSo-Import:2015-04-17:1296
Keywords: Innovation

The networking behavior of Indian executives under environmental uncertainty abroad: An exploratory analysis - Srivastava, Mohit; Moser, Roger; Hartmann, Evi (Journal of Business Research, 2018)
Focused networking has become a significant source of effective internationalization. Prior research has shown that networking can improve the internationalization performance of companies, as local contacts provide access to relevant information that is typically unavailable otherwise. Several factors, such as the level of environmental uncertainty faced abroad, can significantly affect the optimal networking of senior executives in foreign markets. However, there is a lack of research about how environmental uncertainty affects ideal networking behavior. In this study, we examined the impact of the fit between environmental uncertainty and the networking behavior of Indian executives on the internationalization performance of their companies. We collected data from 197 Indian executives with significant experience in European and other markets to test our model. We examined five potential environmental uncertainty factors, including the FDI-related environment, the macroeconomic environment, the material and infrastructure environment, the consumption environment and the competitive environment, as well as four networking behavior dimensions, including proactivity, commitment, strategy and tie strength. The results from a profile deviation analysis reveal that ideal networking behavior profiles exist for different types and levels of environmental uncertainty. In summary, the findings from the study provide useful guidelines for Indian and other executives about how to network abroad given different types and levels of environmental uncertainty, and they offer new perspectives to improve the internationalization performance of these executives.
Keywords: Internationalization; Environmental uncertainty; Networking; Profile deviation; Ideal profiles

The Quest for Competitive Advantage: Empirical Evidence of the Role of Resources in a Global Sourcing Context - Jahns, Christopher; Hartmann, Evi; Löckström, M. (68. Wissenschaftliche Jahrestagung des Verbandes der Hochschullehrer für Betriebswirtschaft e.V. (VHB), 2006)
WiSo-Import:2015-04-17:1326
Keywords: Innovation

The Quest for Competitive Advantage: Empirical Evidence of the Role of Resources in a Global Sourcing Context - Jahns, Christopher; Hartmann, Evi; Lockström, M.; Bals, Lydia (Die Unternehmung, 2007)
This study uses a resource-based research model to empirically investigate how internal resources and the extent of resources acquired through low-cost country sourcing affect purchasing process effectiveness. In addition, the relative importance of different resources was examined. The study was conducted through structured telephone interviews with Chief Procurement Officers and Purchasing Managers of 200 large-sized companies in five European countries (France, Germany, Italy, Spain and the UK). Our empirical results show that purchasing process effectiveness is positively influenced by accessibility to four out of five resource types examined and that differences in importance of resources are observable though not significant. The overall conclusion is that low-cost country sourcing provides access to a larger resource pool, which in turn affects operational performance positively.
WiSo-Import:2015-03-26:1228
Keywords: Innovation

The Relationships between Corporate Entrepreneurship, Supply Chain Resilience and Business Performance: An Empirical Study - Sturm, Sebastian; Hohenstein, Nils-Ole; Hartmann, Evi (Production and Operations Management Society (POMS) 32nd Annual Conference, 2022)
This paper explains how to achieve competitive advantage in dynamic environments by investigating and empirically validating the relationships between corporate entrepreneurship, supply chain resilience and business performance. By combining these distinct but related research fields in a single model, the authors advance cross-disciplinary understanding of supply chain risk management research.<br

The Relevance of Supply Early Warning Systems: A Survey on Its Performance Implications - Jahns, Christopher; Hartmann, Evi; Moder, Marco (Hamburg International Conference of Logistics (HICL), 2006)
WiSo-Import:2015-04-17:1328
Keywords: Innovation

The research landscape around the physical Internet – A bibliometric analysis - Münch, Christopher; Wehrle, Manuel; Meyer, Tobias; Hartmann, Evi (International Journal of Production Research, 2023)
The concept of the Physical Internet (PI) has been introduced as a vision for globally efficient and sustainable logistics. Examining the activities of the PI since its foundation, enormous efforts can be recognised in the political and business spheres. Furthermore, the topic has received considerable attention from logistics and supply chain management scientists. In this context, a wide variety of dimensions of the PI concept has been investigated. In contrast to some existing qualitative literature reviews, this study focuses on a quantitative review methodology to provide a holistic overview of the PI concept and its underlying dimensions and interrelations. Based on bibliometric performance analysis and science mapping, this research maps and connects the extant PI literature landscape. In doing so, the most important journals, researchers, and institutions in the PI field are identified. Furthermore, eight research topics are grouped thematically, including PI benefits and the challenge of its operationalisation, carriers and shippers in the PI network, PI foundations, smart product-service systems and services, hyperconnected city logistics, information and communication technology requirements, modular PI containers, and organisation and control of PI hubs. Based on the clustering of existing research, the study concludes by providing directions for future researc
Keywords: Physical internet; logistics; supply chain management; bibliometric analysis; bibliometric coupling

The Role of Tacit Knowledge in Innovation Management - Seidler‐de Alwis, Ragna; Hartmann, Evi; Gemünden, Hans Georg (20th Industrial Marketing and Purchasing (IMP) conference, 2004)
WiSo-Import:2015-04-17:1338
Keywords: Innovation

The Significance of Tacit Knowledge on Company’s Innovation Capability - Seidler‐de Alwis, Ragna; Hartmann, Evi; Gemünden, Hans Georg (9th International Sympsium for Information Science (ISI), 2004)
WiSo-Import:2015-04-17:1340
Keywords: Innovation

The use of tacit knowledge within innovative companies - Siedler-de Alwis, R.; Hartmann, Evi (31st European International Business Academy (EIBA) conference, 2005)
WiSo-Import:2015-04-17:1337
Keywords: Innovation

The use of tacit knowledge within innovative companies: knowledge management in innovative enterprises - Seidler‐de Alwis, Ragna; Hartmann, Evi (Journal of Knowledge Management, 2008)
Purpose – The purpose of this paper is to examine the use of tacit knowledge within innovative organizations. It addresses what organizations can do to promote knowledge sharing in order to improve successful innovation. Compared to available research material on explicit knowledge, the use of tacit knowledge within companies is relatively unexplored. The use of tacit knowledge is assessed with special emphasis on its significance and implications in the innovation process. Design/methodology/approach – Existing research is structured with the objective of examining how companies make use of tacit knowledge. Key levers for tacit knowledge management are identified and the positive impact of tacit knowledge on innovation success disclosed. Findings – The role of tacit knowledge in innovation management is analysed. Creation, availability and transfer of tacit knowledge within an organization are highlighted. Competitive advantage will be gained when companies value their tacit knowledge because explicit knowledge is knowledge we are already aware of and is public by its nature. Tacit knowledge can be the source of a huge range of opportunities and potentials that constitute discovery and creativity. Practical implications – As this paper focuses on the transfer of tacit knowledge, barriers to successful knowledge transfer are described and success factors are explored which help to secure and improve the transfer of tacit knowledge. Originality/value – It is proven that tacit knowledge has a crucial influence on the success of innovation processes in companies and plays a vital role as a company resource and success factor.
WiSo-Import:2015-03-26:1225
Keywords: Tacit knowledge; Knowledge management; Innovation

Top and bottom line relevance of purchasing and supply management - Hartmann, Evi; Kerkfeld, Dieter; Henke, Michael (Journal of Purchasing and Supply Management, 2012)
Getting a substantial value addition out of investments in purchasing and supply management (PSM) is of central importance to senior management. However, the empirical evidence of a financial value contribution is fragmented. The current study addresses this fragmentation by using a comprehensive performance measurement model to validate empirically (a) whether PSM contributes to the company's financial success and (b) whether the financial value contribution is mediated by benefits of three operational performances (cost, quality, and innovation performance). Our findings from an international survey of 306 major companies from eight industry sectors suggest that an advanced, comprehensive implementation of PSM activities contributes to an improvement in PSM outcomes, which in turn mediates company success. © 2012 Elsevier Ltd.
WiSo-Import:2015-03-26:4548
Keywords: Interviewing/survey; Performance measurement; Purchasing and supply management; Structural equation modelling

Towards Sustainable Freight Transportation - A Risk Framework Application to Truck Platooning - Münch, Christopher; Benz, Lukas; Hartmann, Evi (Logistics Management, 2021)
National and international authorities, specifically the European Commission, have set challenging targets for the reduction of carbon emissions. Transportation is an important lever for emission reduction due to the share of over one quarter of the total emissions in Europe. In particular, road transportation, which accounts for 75% of the transported goods, offers saving potential. The improvement of traffic flows has been identified as a field for prospective energy consumption reduction, among others, by automation, especially platooning. Truck platooning has been discussed from a technical perspective, as well as with a focus on advantages. Risks have so far been included by some authors but not examined holistically. To close this research gap, a case study was conducted in this article to investigate the risks associated with platooning. For this purpose, eight semi-structured interviews were conducted with experts from logistics service providers and truck manufacturers. Eighteen risks were identified and classified into six dimensions (economic, social, legal, IT-related, technical, and ecological), resulting in a risk framework. The results extend the research on truck platooning by clarifying the risk perspective of this concept and provide a starting point for a discussion on the feasibilit

Trade credit, cost of capital and the role of buyer market power from an agency-theory perspective - Liebl, John; Plewa, Markus; Hartmann, Evi (DSI Annual Meeting 2016, 2016)

Transfer of Tacit Knowledge towards Innovation - Hartmann, Evi; Seidler‐de Alwis, Ragna (Innovation Management in Global Networks - A Challenge and Chance for Top-Management, 2006)
Purpose The purpose of this paper is to examine the use of tacit knowledge within innovative organizations. It addresses what organizations can do to promote knowledge sharing in order to improve successful innovation. Compared to available research material on explicit knowledge, the use of tacit knowledge within companies is relatively unexplored. The use of tacit knowledge is assessed with special emphasis on its significance and implications in the innovation process.   Design/methodology/approach Existing research is structured with the objective of examining how companies make use of tacit knowledge. Key levers for tacit knowledge management are identified and the positive impact of tacit knowledge on innovation success disclosed.   Findings The role of tacit knowledge in innovation management is analysed. Creation, availability and transfer of tacit knowledge within an organization are highlighted. Competitive advantage will be gained when companies value their tacit knowledge because explicit knowledge is knowledge we are already aware of and is public by its nature. Tacit knowledge can be the source of a huge range of opportunities and potentials that constitute discovery and creativity.   Practical implications As this paper focuses on the transfer of tacit knowledge, barriers to successful knowledge transfer are described and success factors are explored which help to secure and improve the transfer of tacit knowledge.   Originality/value It is proven that tacit knowledge has a crucial influence on the success of innovation processes in companies and plays a vital role as a company resource and success factor.
WiSo-Import:2015-04-20:1267
Keywords: Innovation

Transforming resilience in the context of a pandemic: results from a cross-industry case study exploring supply chain viability - Münch, Christopher; Hartmann, Evi (International Journal of Production Research, 2022)
Lately, there has been increased interest among researchers in studying the resilience of manufacturing supply chains. However, the Covid-19 pandemic has caused severe disruptions in global supply chains, which have led to calls for greater resilience in these supply chains. This study provides insights into the impact of the Covid-19 pandemic on supply chain resilience by conducting a multiple case study in three intertwined industries based on the dynamic capability view and the relational capability view as a theoretical underpinning. Data were collected during the pandemic in a two-stage interview process with 18 supply chain and production experts directly involved in crisis management. Internal and external documents supplemented the interviews. The results revealed seven higher-level capability groups for building resilience in intertwined supply chains during a pandemic outbreak: agility, collaboration, digital preparedness, flexible redundancy, human resource management, contingency planning, and transparency and visibility. Each capability group is supported by associated capabilities extracted from the data analysis. The findings obtained based on the results of the multiple case study are discussed, and implications for management and future research directions are presente
Keywords: Disruption management; dynamic capabilities view; relational view; supply chain disruption; supply chain resilience; viability

Truck Sharing: Keine Laster - keine Hilfe - Hirschinger, Micha; Moser, Roger; Hartmann, Evi (Wirtschaftswissenschaftliches Studium, 2015)
In vielen Regionen der Welt scheint die zunehmende Zahl der menschengemachten und der Naturkatastrophen die Errungenschaften des 21. Jahrhunderts zu bedrohen, wenn nicht zunichte zu machen. Beben, Fluten, Hungersnöte, Bürgerkriegsfolgen und Flüchtlingsdramen erhöhen die Anforderungen und Ansprüche an die Humanitäre Logistik. Insbesondere die häufigen Probleme auf der letzten Meile erfordern einen neuen Ansatz für den Transport in der humanitären Hilfe. Kann Truck Sharing einen Paradigmenwechsel für die Humanitäre Logistik bewirke
Keywords: Logistik; Supply; Chain; Management; Truck; Sharing

Überschätzte Zusammenarbeit - Jahns, Christopher; Hartmann, Evi; Wagner, A. (Absatzwirtschaft : Zeitschrift für Marketing, 2007)
WiSo-Import:2015-03-26:1240
Keywords: Innovation

Uncovering the Supplier Selection Knowledge Structure: A systematic citation network analysis from 1991 to 2017 - Wetzstein, Anton; Feisel, Edda; Hartmann, Evi; Benton jr., W.C. (Journal of Purchasing and Supply Management, 2018)

Understanding the role of perceived ownership in access-based services: Insights from an analysis of mobility service offerings - Roßmann, Bernhard; Hartmann, Evi; Moser, Roger (VHB Tagung 2017, 2017)
The phenomena of access-based services and related concepts underline the recent rise of the Service Dominant logic in the management literature. However, the resulting variety of access-based models increasingly fragments property rights in practice and therefore blurs the line between ownership and access. This paper aims to address these fuzzy lines in the context of access-based services. For this purpose, subjective feelings of ownership that are based on psychological ownership theory are conceptualised as the missing link between those lines. While a perception of ownership may result in an increase of value attribution from users, burdens of ownership may also be imposed. To explore the role of perceived ownership in access-based services, a taxonomy that integrates both traditional as well as recently established access-based services is developed. As the determinants of perceived ownership are highly contextual, the taxonomy development is carried out within the context of mobility services. Such services involve high levels of value attributions based on psychological perceptions and emotions and might be comparable to other access-based services. In our analysis, features that alter a consumer’s experience during access compared to ownership are interpreted as the determinants of perceived ownership and identified by a review of the access-based mobility service literature. An analysis and comparison of access-based services highlights the enabling effects of technology advances and shifting effects of new preferences in consumer behaviour. To conclude, resulting effects on perceived value attributions within access-based services and suggestions on the role of perceived ownership in future research on access-based services are discusse

Understanding the Role of Supplier Selection in PSM Research – A Systematic Literature Review - Wetzstein, Anton; Hohenstein, Nils-Ole; Hartmann, Evi (Academy of Management Journal, 2015)
With the growth in outsourcing in various sectors, the PSM function and its selection of suppliers are becoming critical to a firm’s business success. However, a thorough analysis of the extensive spectrum of supplier selection (SS) literature has not yet been performed. To address this gap, we conduct a comprehensive and systematic literature review (SLR). The purpose is to profoundly examine the evolution of the exhaustive body of research in SS, its research streams (RS) and to propose areas for further research. To this end, we developed an analytical frame-work that contains six RS derived from the extant literature through our SLR. Results reveal tremendous scientific progress in SS in the last two decades, a trend predicted to continue. Moreover, the findings show that particular categories have been strongly researched whereas other important aspects lack examination. The study presents a large-scale longitudinal overview of 158 papers published in major journals between 1990 and 2013. Extant academic work is to show the importance of SS issues within SCM research. Finally, areas for further research guide potential future investigation. Strategic Supplier Selec
Keywords: Strategic; Supplier; Selection; Framework

Upstream Supply Chain Risk Management: Model Development and Empirical Analysis - Kern, Daniel; Hartmann, Evi; Moser, Roger; Moder, Marco (Academy of Management Annual Meeting, 2010)
WiSo-Import:2015-04-17:1282
Keywords: Innovation

"Verwirrende Lage" - Münch, Christopher; Hartmann, Evi (2022)

What constitutes a born global firm? - Bals, Lydia; Berry, Heather; Hartmann, Evi (Academy of International Business Annual Meeting, 2009)
WiSo-Import:2015-04-17:1284
Keywords: Innovation

What Do We Know About Going Global Early? Liabilities of Foreignness and Early Internationalizing Firms - Bals, Lydia; Berry, Heather; Hartmann, Evi; Rättich, Gordian (Advances in International Management, 2013)
In this chapter, we embrace the recent phenomenon of early internationalizing firms with the goal of understanding these firms in light of decades of research on multinational firms, which has long stressed liabilities of foreignness. It is often implicitly assumed that the only way to reduce liabilities of foreignness is by doing business in foreign markets and learning about the local business environment. However, in this chapter, we focus on several distinctive antecedent firm characteristics that have been shown to facilitate early international expansion by firms, but which are not commonly considered in the international business literature. We perform a systematic review of the literature on early internationalizing firms (following David & Han, 2004), based on the seminal work of Oviatt and McDougall (1994) to guide our analysis of early internationalizing firms and to identify important ways in which these firms differ from multinational firms. We argue that long-standing arguments about the impact of liabilities of foreignness on firm foreign expansion apply to newly internationalizing firms, but that these liabilities are reduced by the experiences and knowledge of the founders and top managers in these firms acquired prior to the inception of these firms. Copyright © 2013 by Emerald Group Publishing Limited All rights of reproduction in any form reserved.
WiSo-Import:2015-04-20:4545